Lithium ion secondary battery, preparation method and electric device

By introducing alkyne alkali additives containing carbon-carbon triple bonds and Lewis alkali-based alia heterocyclic rings into the electrolyte of lithium-ion secondary batteries, and controlling the Dv3 of the positive electrode active material, the problem of degradation of lithium-ion secondary batteries in a high-temperature environment is solved, and the performance of high-temperature and room-temperature performance is achieved.

CN119890415AActive Publication Date: 2025-04-25CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510378592.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-25
Estimated Expiration
2045-03-28

AI Technical Summary

Technical Problem

The performance of existing lithium-ion secondary batteries is degraded in high-temperature environments, and the room temperature performance is affected by high-temperature additives, making it difficult to improve both high-temperature and room temperature performance at the same time.

Method used

The alkyne alkali additive containing carbon-carbon triple bond and Lewis alkali-based azo-heterocyclic ring is introduced into the electrolyte, and the Dv3 of the positive electrode active material is controlled to be within the range of 1 μm or above to improve the high-temperature performance of the battery and suppress the increase in the interface impedance of the negative electrode.

Benefits of technology

It significantly improves the high-temperature performance of lithium-ion secondary batteries, while maintaining good room temperature performance, extends the battery cycle life and reduces the battery internal resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890415A_ABST
    Figure CN119890415A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium ion secondary battery, a preparation method and an electric device. The lithium ion secondary battery comprises a positive pole piece, a negative pole piece and electrolyte, wherein an isolating membrane is arranged between the positive pole piece and the negative pole piece; the positive pole piece comprises a positive active layer, and the positive active layer comprises a positive active material; the electrolyte comprises electrolyte salt, a non-aqueous solvent and an additive; the positive electrode active material comprises a lithium transition metal oxide positive electrode material, and the Dv3 of the positive electrode active material is greater than or equal to 1 [mu] m; the additive comprises a first additive, and the first additive is an alkyne alkali additive containing Lewis base nitrogen heterocyclic rings. The lithium ion secondary battery has relatively good normal temperature performance under the conditions of relatively high energy density and remarkably improved high temperature performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion secondary batteries, and further to lithium-ion secondary batteries, preparation methods and electrical devices. Background Art

[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.

[0003] With the development of lithium-ion secondary battery technology, lithium-ion secondary batteries are increasingly widely used in smart phones, tablet computers, laptops, power tools, electric bicycles, electric motorcycles, electric vehicles, aerospace and other fields, and are also widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations. In order to meet the growing demand for endurance, battery systems with high energy density have always been an important research direction. In the storage and use of lithium-ion secondary batteries, not only room temperature environments are involved, but also high temperature scenes are usually inevitably involved. Non-limiting examples include high temperature storage and / or use environments such as summer temperature rise, exposure to the sun, and near the equator. High-temperature additives such as acetylene additives can improve the high temperature performance of the battery by optimizing the negative electrode solid electrolyte interface (SEI) film, but will lead to an increase in the negative electrode interface impedance, affecting the normal temperature performance.

[0004] Therefore, it is necessary to develop new methods to improve the high temperature performance of high energy density battery systems while maintaining good room temperature performance. Summary of the invention

[0005] According to various embodiments and examples of the present application, a lithium ion secondary battery, a preparation method and an electric device are provided. The lithium ion secondary battery has a high energy density and significantly improved high temperature performance, and also has good room temperature performance.

[0006] In some embodiments of the first aspect of the present application, a lithium ion secondary battery is provided, which includes a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein a separator is provided between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet includes a positive electrode active layer, and the positive electrode active layer includes a positive electrode active material; the electrolyte includes an electrolyte salt, a non-aqueous solvent and an additive;

[0007] The positive electrode active material comprises a lithium transition metal oxide positive electrode material. v 3 greater than or equal to 1 μm;

[0008] The additives include a first additive, which is an acetylene base additive containing a Lewis base nitrogen heterocycle.

[0009] For a high energy density battery system containing a lithium transition metal oxide positive electrode material as the positive electrode active material, the high temperature performance of the battery can be significantly improved by introducing a first additive containing a carbon-carbon triple bond and a Lewis base nitrogen heterocycle into the electrolyte. v 3 Control in a relatively high value range (such as D v 3 is greater than or equal to 1 μm), the small-sized particles with smaller particle size and larger specific surface area in the positive electrode active material can be controlled at a lower content, which significantly reduces the interfacial side reactions of the positive electrode and significantly reduces the dissolution of transition metal ions of the positive electrode; thus, through the aforementioned multiple synergistic effects, the increase in interfacial impedance that may be caused by the first additive participating in the negative electrode film formation can be significantly suppressed, thereby significantly improving the high-temperature performance of the high-energy density battery system while also having good room-temperature performance.

[0010] The mechanism by which the first additive significantly improves the high-temperature performance of the battery includes but is not limited to the following aspects: the first additive can participate in the formation and repair of the solid electrolyte interface (SEI) film at the negative electrode, the first additive and the SEI film formed by it have high-temperature stability, which can significantly improve the stability of the SEI film at high temperature and reduce the interface side reactions of the negative electrode; Lewis base nitrogen heterocycles can also be used to absorb acid byproducts (such as hydrofluoric acid) produced by electrolyte side reactions from the source, thereby inhibiting the acid byproducts from damaging the positive and negative electrode interface films and reducing the positive and negative electrode interface side reactions; the acid byproducts can also be used to inhibit the damage to the positive electrode active material and reduce the dissolution of transition metal ions at the positive electrode, and the carbon-carbon triple bond can be used to adsorb transition metal ions that may be dissolved from the positive electrode, thereby significantly reducing the deposition of transition metal ions at the negative electrode and significantly reducing the damage to the negative electrode SEI film by transition metal ions that may be dissolved from the positive electrode; the acid byproducts can also be used to inhibit the damage to the negative electrode SEI film, further improving the stability of the negative electrode SEI film and reducing the negative electrode interface side reactions.

[0011] In some embodiments, the D of the positive electrode active material v 3 is 1μm~2μm, and can be selected as 1μm~1.6μm.

[0012] By increasing the D v 3 Controlling within the aforementioned range is conducive to better controlling the content of small-sized particles with smaller particle size and larger specific surface area in the positive electrode active material, thereby better reducing the interfacial side reactions of the positive electrode, and can better be based on the multiple synergistic effects of the positive electrode active material and the first additive in the electrolyte, which is conducive to better significantly improving the high-temperature performance while also taking into account good room-temperature performance.

[0013] In some embodiments, the average particle size of primary particles in the positive electrode active material is 1.1 μm to 3.0 μm.

[0014] In some embodiments, the average particle size of primary particles in the positive electrode active material is 1.2 μm to 2.5 μm.

[0015] By controlling the average particle size of the primary particles in the positive electrode active material (denoted as D1) within the aforementioned range, it is beneficial to make the primary particles in the positive electrode active material have a more suitable size, which can not only control the positive electrode active material to have a more suitable ion transmission path, but also better inhibit the positive electrode interface reaction, reduce the dissolution of transition metal ions and their damage to the negative electrode SEI film, and then control the negative electrode film formation consumption of acetylene base additives, thereby improving the cycle performance of lithium-ion secondary batteries and inhibiting the increase in battery internal resistance. Based on the synergy of the aforementioned effects, but not limited to the aforementioned theory, it is beneficial to better coordinate the control of the structural stability of the positive electrode active layer, the internal resistance of the battery and the consumption of acetylene base additives participating in the negative electrode film formation, which is beneficial to better significantly improve the high temperature performance while taking into account good room temperature performance.

[0016] In some embodiments, the D of the positive electrode active material v The ratio of 50 to the average particle size of the primary particles in the positive electrode active material is recorded as B1;

[0017] The positive electrode sheet meets one or more of the following characteristics:

[0018] (a1) D of the positive electrode active material v 50 is 2.5μm~ 5μm;

[0019] (a2) B1 is 1~2.5.

[0020] In some embodiments, the positive electrode plate satisfies one or more of the following characteristics:

[0021] (a1') D of the positive electrode active material v 50 is 3μm~4.5μm;

[0022] (a2')B1 is 1.8~2.3.

[0023] By increasing the D v 50 is controlled within the aforementioned range, which is conducive to making the positive electrode active material have a more suitable particle size distribution, and can indirectly adjust the contact area between the positive electrode active material and the electrolyte, which is conducive to better inhibiting the interface side reaction between the positive electrode active material and the electrolyte during the cycle and / or storage process, reducing the dissolution of the positive electrode transition metal ions, thereby better improving the cycle performance of the lithium ion secondary battery and inhibiting the increase of the battery internal resistance; it is also conducive to better controlling the ion transmission path of the positive electrode active material particles as a whole; based on the synergy of the aforementioned effects, but not limited to the aforementioned theory, it is conducive to better improving the high temperature performance while taking into account the good room temperature performance.

[0024] By increasing the D v When the ratio (B1) of 50 to the average particle size of the primary particles in the positive electrode active material is controlled within the aforementioned range, it is beneficial to make the median particle size of the positive electrode active material particles close to the average particle size of the primary particles as the basic unit of the particles, thereby reducing the agglomeration ratio of the primary particles in the positive electrode active material, reducing the content of the secondary particles as the primary particle agglomerates, and correspondingly increasing the proportion of non-agglomerated primary particles; compared with the secondary particles with primary particle interfaces, the non-agglomerated primary particles do not have primary particle interfaces in the secondary particles, so that the non-agglomerated primary particles can better resist the risk of particle cracking during the cycle and / or storage process; it is also beneficial to better control the ion transmission path of the positive electrode active material particles as a whole; by controlling B1 within the aforementioned range, the structural stability of the positive electrode active material can be better improved, which is more conducive to reducing the positive electrode interface side reactions and slowing down the electrolyte consumption, reducing the dissolution of the positive electrode transition metal ions, and is more conducive to improving the battery life and inhibiting the increase of the battery internal resistance, which is conducive to better improving the high temperature performance while taking into account the good room temperature performance.

[0025] By synergistically controlling the D v 50 (or B1) and the average particle size of the primary particles in the positive electrode active material are beneficial to taking into account the ion transmission path of the primary particles and the particles as a whole in the positive electrode active material, and at the same time better inhibiting the positive electrode interface side reaction. Based on the synergy of the aforementioned effects, but not limited to the aforementioned theory, it is beneficial to better control the internal resistance of the battery, and is beneficial to better take into account good room temperature performance while significantly improving the high temperature performance.

[0026] In some embodiments, the negative electrode sheet includes a negative electrode active layer, and the negative electrode active layer includes a negative electrode active material; v 50 is 8μm~20μm.

[0027] In some embodiments, the D of the negative electrode active material v 50 is 10μm~18μm.

[0028] By increasing the D v When 50 is controlled within the aforementioned range, the specific surface area of ​​the negative electrode active material can be controlled within a relatively low range, which is beneficial to reducing the negative electrode interface side reactions, reducing or delaying the negative electrode interface consumption of the first additive, and is also beneficial to better control the ion transmission path of the negative electrode active material particles as a whole. Based on the synergy of the aforementioned effects, but not limited to the aforementioned theory, it is beneficial to better control the internal resistance of the battery, and is beneficial to better improve the high temperature performance while taking into account good room temperature performance.

[0029] In some embodiments, the negative electrode plate includes a negative electrode active layer, and the negative electrode active layer includes a negative electrode active material; the negative electrode active material includes at least one of a carbon-based material and a silicon-based material;

[0030] The negative electrode plate meets one or more of the following characteristics:

[0031] (b1) The mass proportion of the silicon-based material in the negative electrode active material is 0-30%;

[0032] (b2) The silicon-based material includes a silicon-carbon composite material, which includes a porous carbon matrix and elemental silicon located in the pores of the porous carbon matrix; the mass proportion of the silicon-carbon composite material in the silicon-based material is 80% to 100%.

[0033] By controlling the content and / or type of silicon-based materials in the negative electrode active material within the aforementioned range, it is beneficial to better control the expansion and contraction changes of the negative electrode, reduce the generation of fresh interfaces, inhibit negative electrode interface side reactions, reduce the consumption rate of the first additive, reduce the growth rate of battery internal resistance, and improve the battery life. For example, among silicon-based materials, the volume expansion and contraction changes of silicon-carbon composite materials are relatively low.

[0034] In some embodiments, the mass percentage of the first additive in the electrolyte is less than 3.6%.

[0035] In some embodiments, the mass percentage of the first additive in the electrolyte is 0.02% to 3.6%.

[0036] In some embodiments, the mass percentage of the first additive in the electrolyte is 0.02% to 2%.

[0037] In some embodiments, the mass percentage of the first additive in the electrolyte is 0.1% to 1.6%, and can be optionally 0.1% to 1.2%.

[0038] By controlling the mass proportion of the first additive in the electrolyte within the aforementioned range, the first additive can continue to play a role in repairing the SEI film during circulation and / or storage, which is more conducive to significantly improving high-temperature performance while also taking into account good room-temperature performance.

[0039] In some embodiments, the additive includes a negative electrode film-forming additive different from the first additive.

[0040] The negative electrode film-forming additive different from the first additive can competitively participate in the negative electrode film formation, can reduce or delay the negative electrode film formation consumption of the first additive, and can inhibit the increase in the negative electrode interface impedance caused by the participation of the first additive in the negative electrode film formation, which is conducive to better improving the high temperature performance of the high energy density battery system while also having good room temperature performance.

[0041] In some embodiments, the additive includes one or more of a second additive, a third additive, and a fourth additive;

[0042] The second additive is one or more of a silane additive and a siloxane additive;

[0043] The third additive is one or more of an isocyanate additive and an acid anhydride additive;

[0044] The fourth additive is one or more of a lithium salt additive and a phosphate ester additive.

[0045] In some embodiments, in the electrolyte, the mass ratio of the second additive to the first additive is 0.1-50.

[0046] In some embodiments, in the electrolyte, the mass ratio of the third additive to the first additive is 0.01-50.

[0047] In some embodiments, in the electrolyte, the mass ratio of the fourth additive to the first additive is 0.1-100.

[0048] In some embodiments, in the electrolyte, the mass ratio of the second additive, the third additive, the fourth additive and the first additive is (0-0.5):(0-0.5):(0-1):1.

[0049] The second additive, the third additive and the fourth additive can all be used as negative electrode film-forming additives. The second additive is a type of additive with low negative electrode film-forming impedance and a certain acid removal effect. Its acid removal effect is lower than that of the first additive, and its negative electrode film-forming impedance is lower than that of the first additive. The third additive is a type of additive with a good acid removal effect. Its acid removal effect is better than that of the first additive, but its negative electrode film-forming impedance is higher than that of the first additive. The negative electrode film-forming impedance of the fourth additive is very low, much lower than that of the first additive.

[0050] Utilizing the synergistic effect of the first additive and one or more of the second additive, the third additive and the fourth additive is beneficial to better improve the high temperature performance while also taking into account good room temperature performance.

[0051] In some embodiments, the electrolyte satisfies one or more of the following characteristics:

[0052] (c1) the molecular weight of the first additive is less than or equal to 500 Da;

[0053] (c2) the molecule of the first additive contains 1 to 4 carbon-carbon triple bonds;

[0054] (c3) the carbon-carbon triple bond is CH≡C-;

[0055] (c4) the first additive contains 1 to 4 Lewis base nitrogen heterocycles in its molecule;

[0056] (c5) the Lewis base nitrogen heterocycle includes an imidazole ring;

[0057] (c6) In the molecule of the first additive, the carbon-carbon triple bond and the Lewis base nitrogen heterocycle are connected by a linker L 1 connected, the linking group L 1 Contains C covalently bonded to a carbon-carbon triple bond 1-3 Alkylene or containing a fluorinated C covalently bonded to a carbon-carbon triple bond 1-3 Alkylene.

[0058] In some embodiments, the first additive satisfies one or more of the following characteristics:

[0059] (d1) the molecular weight of the first additive is less than or equal to 300 Da;

[0060] (d2) the first additive contains 1 to 4 imidazole rings in its molecule;

[0061] (d3) the linking group L 1 Contains C covalently bonded to a carbon-carbon triple bond 1-3 Alkylene;

[0062] (d4) The Lewis base nitrogen heterocycle includes an imidazole ring; the imidazole ring in the Lewis base nitrogen heterocycle is substituted by 0, 1 or more substituent groups Q 2 The substituent group Q in the substituted imidazole group is 2 Each independently is C 1-3 an alkyl group, a cyano group or a fluorine atom.

[0063] In some embodiments, the first additive includes a compound II having a structure as shown in formula (II): Among them, L 11 C 1-3 Alkylene, Q 2 Independently for C 1-3 Alkyl, cyano or fluorine atom, p2 is 0, 1, 2 or 3;

[0064] The mass proportion of the compound II in the first additive is 80% to 100%.

[0065] By controlling the molecular weight of the first additive within the aforementioned lower range, the first additive can have a smaller molecular size, which is beneficial for better controlling the low viscosity characteristics of the electrolyte, making the electrolyte have a higher conductivity, and better controlling the internal resistance of the battery.

[0066] By controlling the number of carbon-carbon triple bonds in the first additive within the aforementioned range, it is beneficial to suppress the increase in interfacial impedance caused by the first additive participating in the formation and repair of the SEI film, and it is also beneficial to control the influence of the first additive on the liquid phase impedance; thereby, the increase in battery internal resistance can be better suppressed.

[0067] By controlling the amount of the Lewis base nitrogen heterocycle in the first additive within the aforementioned range, it is beneficial to better absorb the acid byproducts in the electrolyte, and it is also beneficial to control the steric effect of the Lewis base nitrogen heterocycle on the carbon-carbon triple bond.

[0068] An example of the Lewis base nitrogen heterocycle is the imidazole ring in compound II.

[0069] In some embodiments of the second aspect of the present application, a method for preparing a lithium ion secondary battery is provided, comprising the following steps:

[0070] An electrode assembly including a positive electrode sheet, a separator and a negative electrode sheet is placed in a battery housing; wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet; wherein the positive electrode sheet includes a positive electrode active layer, the positive electrode active layer includes a positive electrode active material, the positive electrode active material includes a lithium transition metal oxide positive electrode material, and the D v 3 greater than or equal to 1 μm;

[0071] An electrolyte is injected into the battery housing, and the electrolyte is allowed to stand to allow the electrolyte to soak the positive electrode plate and the negative electrode plate to form an electrolyte; wherein the electrolyte includes an electrolyte salt, a non-aqueous solvent and an additive; the additive includes a first additive, and the first additive is an acetylene base additive containing a Lewis base nitrogen heterocycle.

[0072] The prepared lithium ion secondary battery has the advantages of the lithium ion secondary battery described in the first aspect of the present application.

[0073] In some embodiments, the lithium ion secondary battery described in the first aspect of the present application is prepared.

[0074] In some embodiments of the third aspect of the present application, an electrical device is provided, which includes the lithium-ion secondary battery described in the first aspect of the present application.

[0075] Details of one or more implementations or embodiments of the present application are set forth in the following drawings and description. Other features, objects, and advantages of the present application will become apparent from the description, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] In order to better describe and illustrate the embodiments, examples or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments, examples or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0077] Figure 1 It is a schematic diagram of a battery cell according to an embodiment of the present application.

[0078] Figure 2 for Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown.

[0079] Figure 3 FIG. 1 is a schematic diagram of a battery device according to an embodiment of the present application.

[0080] Figure 4 A schematic diagram of a battery pack according to an embodiment of the present application.

[0081] Figure 5 for Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0082] Figure 6 A schematic diagram of an electrical device using a lithium-ion secondary battery according to an embodiment of the present application as a power source.

[0083] Description of reference numerals:

[0084] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery device; 5. Battery cell; 51. Battery casing; 52. Electrode assembly; 53. Cover plate; 6. Electrical device. DETAILED DESCRIPTION

[0085] Below, some embodiments and examples of the lithium-ion secondary battery, preparation method and electrical device of the present application are described in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0086] "Scope" disclosed in the present application can be limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or excluding end values, and any end value can be included or not included independently, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are also listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation for these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to listing the parameter as, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.

[0087] In the present application, "numerical value" is involved, and its meaning includes the present number and its reasonable approximation. The definition of "numerical value" can be applied to discrete numerical points and the endpoints of the numerical range. If not specifically limited, "approximation" is involved, covering the numerical interval based on the reasonable fluctuation range of the present number, and the reasonable fluctuation range may vary due to the type and numerical size of the present number. The reasonable fluctuation range can be reasonably confirmed according to the accuracy of the test or measurement method. Therefore, when it comes to numerical values ​​or numerical ranges, if there is no special explanation, it should be understood that the numerical value covers its reasonable approximation, and the numerical range covers the reasonable approximation of the two endpoints. Those skilled in the art can understand that the acceptable fluctuation range of the relevant approximation can be included in the definition of the numerical value or the numerical range. In the present application, if there is no other explanation, "N1" can be reasonably understood as "about N1", and "N1~N2" can be reasonably understood as "about N1 to about N2", wherein N1 and N2 are two unequal numerical values.

[0088] In this application, unless otherwise specified, "about" means within a reasonable range above and below the number, and the fluctuation range may vary depending on the type and value of the number. For example, it may be allowed to be within a range of ±10%, ±5%, ±2%, ±1%, etc. For example, taking "about 20°C" and its approximate value of ±1°C as an example, the approximate values ​​of 19°C, 19.5°C, etc. within the approximate range shown in "about 20°C" should also be included in the range indicated by "about 20°C".

[0089] In this application, when "multiple", "multiple", "multiple" and the like are involved, unless otherwise specified, they refer to a number greater than or equal to 2. For example, "one or more" means one or ≥ (greater than or equal to) two. It is understood that when "any number" of items are involved, it refers to any suitable combination of multiple items, that is, the combination of "any number" of items is performed in a manner that does not conflict and can implement this application.

[0090] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0091] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.

[0092] Those skilled in the art will appreciate that in the methods of the various embodiments or embodiments of the present application, if not particularly limited, the order of writing of each step does not mean a strict execution order and constitutes any limitation to the implementation process, and the detailed execution order of each step should be determined by its function and possible internal logic. If there is no special description, all steps of the present application can be performed in sequence, or can be performed randomly, and can preferably be performed in sequence. For example, method M includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed in sequence, or steps (b) and (a) performed in sequence. For example, method M may also include step (c), indicating that step (c) can be added to method M in any order, for example, method M may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.

[0093] In the present application, in the open technical features or technical solutions described by the words "contain", "include", "include", etc., if there is no other explanation, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, a includes a1, a2 and a3. If there is no other explanation, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "a consists of a1, a2 and a3" or "a is selected from a1, a2 and a3", and the feature or solution of "a includes not only a1, a2 and a3, but also other members".

[0094] In the present application, unless otherwise specified, M (such as m1) means that m1 is a non-limiting example of M, and it can be understood that M is not limited to m1.

[0095] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel solutions of "yes" or "no". If there are multiple "optional" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent. Unless otherwise specified, the descriptions of "optionally include", "optionally include", etc. in this application, taking "optionally include" as an example, mean "may include or not include".

[0096] In the present application, unless otherwise specified, the features or solutions corresponding to "and / or" include any one of two or more related listed items, and also include any and all combinations of the related listed items, wherein any and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "M and / or N" means a group consisting of M, N, and "a combination of M and N". Among them, "including M and / or N" can mean "including M, including N, and including M and N", and can also mean "including M, including N, or including M and N", which can be properly understood according to the sentence in which it is located.

[0097] Herein, the word “suitable” in “suitable combination”, “suitable method”, etc., shall be based on the technical solution that can implement the present application.

[0098] Herein, "preferred", "better", and "better" are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute a limitation on the scope of protection of this application. If multiple "preferred" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "preferred" item is independent.

[0099] In the present application, “further”, “furthermore”, “particularly”, “for example”, “such as”, “example”, “for example”, etc. are used for descriptive purposes to indicate differences in content, but should not be understood as limiting the scope of protection of the present application.

[0100] In the present application, the terms "first", "second", "third", etc. in "the first aspect", "the second aspect", "the third aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0101] In this application, unless otherwise clearly specified or limited, the terms "connected" and "connection" related to mechanical structures should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection. For ordinary technicians in this field, the meanings of the above terms in this application can be understood according to the circumstances.

[0102] In the present application, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. In the present application, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean a relative positional relationship in terms of horizontal height, or may mean that there is an attachment relationship without limiting the relative positional relationship in terms of horizontal height.

[0103] In this application, the term "room temperature" generally refers to 4°C to 35°C, and may refer to 20°C ± 5°C. In some embodiments or examples of this application, room temperature refers to 20°C to 30°C.

[0104] In this application, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left endpoint and the right endpoint are the same. For example, 3~5 μm or 3-5 μm both mean that the units of the left endpoint "3" and the right endpoint "5" are both μm (micrometers), which have the same meaning as 3 μm ~5 μm. In addition, similar descriptions of other parameters such as temperature and size are also understood in the same way.

[0105] In this application, unless otherwise specified, the term "molecular weight" refers to the molecular weight measured in Daltons (Da), where 1 Dalton is equal to 12 One twelfth of the atomic mass of C.

[0106] In this application, "greater than or equal to", "greater than or equal to" and "≥" have the same meaning and can be used interchangeably; "less than or equal to", "less than or equal to" and "≤" have the same meaning and can be used interchangeably; "greater than" can be equivalently expressed as ">", and "less than" can be equivalently expressed as "<". In this application, unless otherwise specified, "greater than or equal to" and "≥" can be regarded as providing two solutions of "greater than" and "equal to". In this application, unless otherwise specified, "less than or equal to" and "≤" can be regarded as providing two solutions of "less than" and "equal to".

[0107] In the present application, exemplary descriptions such as "in some implementation modes (or examples)" and "in one implementation mode (or example)" may include but are not limited to the following meanings: these solutions may be combined with other solutions in a suitable manner to form a new technical solution.

[0108] The improved effects described in this application, unless otherwise stated, are not intended to be limited to any theory.

[0109] In order to meet the growing demand for endurance, battery systems with high energy density have always been an important research direction. In the storage and use of lithium-ion secondary batteries, not only room temperature environments are involved, but also high temperature scenes are usually inevitably involved. Non-limiting examples include high temperature storage and / or use environments such as summer temperature rise, exposure to the sun, and near the equator. High-temperature additives such as acetylene additives can improve the high temperature performance of the battery by optimizing the negative electrode solid electrolyte interface (SEI) film, but will lead to an increase in the negative electrode interface impedance, affecting the performance of room temperature performance. Therefore, it is necessary to develop new methods to improve the high temperature performance of high energy density battery systems while maintaining good room temperature performance.

[0110] For traditional lithium-ion secondary batteries, during the battery charging and discharging process, electrolyte side reactions are prone to produce acid byproduct substances, such as hydrofluoric acid, which leads to capacity decay and affects the battery life. For traditional lithium-ion secondary batteries whose positive electrode plates include lithium transition metal oxide positive electrode materials, on the one hand, these acid byproduct substances may destroy the positive electrode solid electrolyte interface film (CEI film) and corrode the positive electrode active material, resulting in the dissolution of transition metal ions from the positive electrode, leading to the deterioration of battery cycle and / or storage performance; on the other hand, these acid byproduct substances are prone to destroy the negative electrode SEI film, exposing a fresh interface, aggravating the interface side reactions of the negative electrode, and also deteriorating the battery cycle and / or performance. Among them, the dissolution of transition metal ions from the positive electrode not only affects the structural stability of the positive electrode active material, but these dissolved transition metal ions migrate to the negative electrode and are easily destroyed after deposition, aggravating the negative electrode interface side reactions, and also deteriorating the battery cycle and / or storage performance.

[0111] According to various implementations and examples of the present application, the present application provides a lithium ion secondary battery, a preparation method and an electric device. The lithium ion secondary battery has a high energy density and significantly improved high temperature performance, and also has good room temperature performance.

[0112] In this application, unless otherwise specified, the "high temperature" during battery cycling and / or storage may be greater than 35°C and less than or equal to 80°C, optionally, greater than 35°C and less than or equal to 60°C, further optionally 37°C to 60°C, further optionally 40°C to 60°C, and further optionally 45°C to 60°C, but not limited thereto. The "high temperature" during battery storage or cycling may also be any of the following temperatures or a range consisting of any two of the following temperatures: 36°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc.

[0113] In this application, unless otherwise specified, the "normal temperature" during battery circulation and / or storage may be 20°C to 35°C, optionally 20°C to 30°C, but not limited thereto. The "high temperature" during battery storage or circulation may also be any of the following temperatures or a range consisting of any two of the following temperatures: 20°C, 22°C, 24°C, 25°C, 26°C, 28°C, 30°C, 32°C, 34°C, 35°C, etc.

[0114] In some embodiments, the lithium-ion secondary battery comprises a positive electrode plate and an electrolyte; the electrolyte comprises an electrolyte salt, a non-aqueous solvent and an additive; the positive electrode plate comprises a positive electrode active layer, and the positive electrode active layer comprises a positive electrode active material; the electrolyte comprises an electrolyte salt, a non-aqueous solvent and an additive; the positive electrode active material comprises a lithium transition metal oxide positive electrode material, and the D of the positive electrode active material v 3 is greater than or equal to 1 μm; the additive includes a first additive, and the first additive is an acetylene base additive containing a Lewis base nitrogen heterocycle. The lithium ion secondary battery has a higher energy density and significantly improved high temperature performance, and also has better room temperature performance.

[0115] In some embodiments, a lithium-ion secondary battery is provided, comprising a positive electrode plate and an electrolyte; the positive electrode plate comprises a positive electrode active layer, the positive electrode active layer comprises a positive electrode active material; the electrolyte comprises an electrolyte salt, a non-aqueous solvent and an additive; the positive electrode active material comprises a lithium transition metal oxide positive electrode material, and the average particle size of the primary particles in the positive electrode active material is 1.1 μm~3.0 μm (also refer to the appropriate numerical value or range in the context); the additive comprises a first additive, and the first additive is an acetylene base additive containing a Lewis base nitrogen heterocycle.

[0116] In this application, unless otherwise specified, the term "lithium-ion secondary battery" refers to a secondary battery whose active ions include lithium ions, and "lithium-ion battery cell" refers to a battery cell whose active ions include lithium ions. Typically, a lithium-ion secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. A separator is provided between the positive electrode sheet and the negative electrode sheet. The separator mainly plays the role of preventing the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0117] In the present application, unless otherwise specified, the "electrode active material layer" includes at least one of the positive electrode active material layer of the positive electrode sheet and the negative electrode active material layer of the negative electrode sheet. Depending on the detailed circumstances, the electrode active material layer may refer to the positive electrode active material layer or the negative electrode active material layer. It can be understood that the positive electrode active material layer contains positive electrode active materials, and the negative electrode active material layer contains negative electrode active materials. In the present application, the "electrode active material layer" may also be recorded as the "active material layer", the "positive electrode active material layer" may also be recorded as the "positive electrode active layer", and the "negative electrode active material layer" may also be recorded as the "negative electrode active layer".

[0118] In this application, the terms "electrode plate" and "electrode plate" have the same meaning and can be used interchangeably. The electrode plate can be a positive electrode plate or a negative electrode plate, and the "active material" or "active substance" in the electrode plate has the ability to reversibly embed and extract active ions.

[0119] In the present application, the term "negative electrode sheet" includes a negative electrode active layer, and the negative electrode active layer includes a negative electrode active material. The term "negative electrode active material" refers to a material used in a negative electrode sheet that can reversibly insert and extract active ions.

[0120] In this application, unless otherwise specified, "negative electrode sheet" includes a negative electrode current collector. "Negative electrode current collector" refers to a structure responsible for collecting and conducting electrons at the negative electrode. In the negative electrode sheet, the negative electrode active layer is located on at least one side of the negative electrode current collector, and can be located on one side or both sides of the negative electrode current collector.

[0121] In the present application, the term "positive electrode sheet" includes a positive electrode active layer, and the positive electrode active layer includes a positive electrode active material. The term "positive electrode active material" refers to a material used in a positive electrode sheet that can reversibly extract and insert active ions.

[0122] In this application, unless otherwise specified, "positive electrode sheet" includes positive electrode current collector. "Positive electrode current collector" refers to the structure responsible for collecting and conducting electrons at the positive electrode. In the positive electrode sheet, the positive electrode active layer is located on at least one side of the positive electrode current collector, and can be located on one side or both sides of the positive electrode current collector.

[0123] In the present application, unless otherwise specified, "separation membrane" and "diaphragm" have the same meaning and can be used interchangeably.

[0124] In a first aspect of the present application, a lithium ion secondary battery is provided. The lithium ion secondary battery has a higher energy density and significantly improved high temperature performance, and also has better room temperature performance.

[0125] In some embodiments, a lithium ion secondary battery is provided, which includes a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein a separator is disposed between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet includes a positive electrode active layer, and the positive electrode active layer includes a positive electrode active material; the electrolyte includes an electrolyte salt, a non-aqueous solvent and an additive; the positive electrode active material includes a lithium transition metal oxide positive electrode material, and the D of the positive electrode active material v 3 is greater than or equal to 1 μm; the additive includes a first additive, and the first additive is an acetylene base additive containing a Lewis base nitrogen heterocycle.

[0126] In the present application, unless otherwise specified, "lithium transition metal oxide positive electrode material" refers to a positive electrode active material containing lithium, transition metal and oxygen. It can be seen that the lithium transition metal oxide positive electrode material includes non-lithium metal elements, and the non-lithium metal elements include transition metal elements. Non-limitingly, in the lithium transition metal oxide positive electrode material, the molar percentage of the transition metal element relative to the non-lithium metal element can be 90% to 100%, and can also be any of the following percentages or a range selected from any two of the following percentages: 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.

[0127] In the present application, unless otherwise specified, “non-lithium metal element” refers to a metal element that is not lithium (Li) element.

[0128] In the context of this application, the volume cumulative distribution particle size D v N (where N represents any value selected from 0 to 100) is used to characterize the particle size of the material, which refers to the particle size corresponding to when the cumulative volume distribution percentage of the material reaches N%, and the particle size is less than or equal to D v The volume percentage of N is N%. v N can be obtained from the volume cumulative distribution curve of the material particle size. If there is no other explanation, the volume cumulative distribution curve starts from zero from the small particle size side. v 50 is used as an example. In this application, unless otherwise specified, D v 50 refers to the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%. This parameter indicates that the particle size of particles accounting for 50% of the volume of the material is less than or equal to D v50, and 50% of the particles by volume are larger than D v 50. Those skilled in the art will appreciate that v 50. D v 3. D v 1, etc., and can be measured by instruments and methods known in the art. For example, it can be conveniently measured by laser particle size analyzer with reference to GB / T 19077-2016 particle size distribution laser diffraction method, such as Mastersizer 2000E laser particle size analyzer and LS-909 laser particle size analyzer (OMEC) of Malvern Instruments Ltd., UK. Further, for equipment models such as Malvern 2000 (MasterSizer 2000) laser particle size analyzer, the standard process GB / T19077-2016 / ISO 13320:2009 can be referred to for testing.

[0129] In the present application, unless otherwise specified, "non-aqueous solvent" refers to a solvent that is not water.

[0130] In the present application, unless otherwise specified, a "carbon-carbon triple bond" is an unsaturated bond having a -C≡C- skeleton.

[0131] In this application, unless otherwise specified, "Lewis base nitrogen heterocycle" refers to a nitrogen heterocycle with Lewis base properties. This concept is based on Lewis acids and bases theory. Lewis base nitrogen heterocycles can donate electron pairs and have electron-rich properties. Therefore, Lewis base nitrogen heterocycles can attract and bind acidic substances. Non-limiting examples of Lewis base nitrogen heterocycles include imidazole rings, but are not limited thereto.

[0132] In the present application, unless otherwise specified, "nitrogen heterocyclic structure" refers to a cyclic structure in which the ring-forming atoms include nitrogen atoms. The term "ring-forming atoms" refers to the constituent atoms of the ring skeleton. As a non-limiting example, the three carbon atoms and two nitrogen atoms in the imidazole ring are ring-forming atoms, and the imidazole ring is a 5-membered ring. "Ring-forming nitrogen atoms" refers to nitrogen atoms in the ring-forming atoms.

[0133] In this application, unless otherwise specified, "first additive" refers to an acetylene base additive containing a Lewis base nitrogen heterocycle; it is understood that the first additive contains a carbon-carbon triple bond. It is understood that the first additive can attract and bind acidic substances, such as acid byproducts in the electrolyte (such as hydrofluoric acid). The first additive can participate in the formation of the negative electrode solid electrolyte interface (SEI) film. The first additive can significantly improve the high temperature performance of the battery, including extending the high temperature cycle and storage life, and can be used as a high temperature additive. However, the introduction of the first additive is likely to lead to a large negative electrode interface impedance at room temperature.

[0134] In the lithium-ion secondary battery provided in the present application, it can be understood that the positive electrode plate and the negative electrode plate are soaked in the electrolyte.

[0135] For a high energy density battery system containing a lithium transition metal oxide positive electrode material as the positive electrode active material, the high temperature performance of the battery can be significantly improved by introducing a first additive containing a carbon-carbon triple bond and a Lewis base nitrogen heterocycle into the electrolyte. v 3 Control in a relatively high value range (such as D v 3 is greater than or equal to 1 μm), the small-sized particles with smaller particle size and larger specific surface area in the positive electrode active material can be controlled at a lower content, which significantly reduces the interfacial side reactions of the positive electrode and significantly reduces the dissolution of transition metal ions of the positive electrode; thus, through the aforementioned multiple synergistic effects, the increase in interfacial impedance that may be caused by the first additive participating in the negative electrode film formation can be significantly suppressed, thereby significantly improving the high-temperature performance of the high-energy density battery system while also having good room-temperature performance.

[0136] The mechanism by which the first additive significantly improves the high-temperature performance of the battery includes but is not limited to the following aspects: the first additive can participate in the formation and repair of the solid electrolyte interface (SEI) film at the negative electrode, the first additive and the SEI film formed by it have high-temperature stability, which can significantly improve the stability of the SEI film at high temperature and reduce the interface side reactions of the negative electrode; Lewis base nitrogen heterocycles can also be used to absorb acid byproducts (such as hydrofluoric acid) produced by electrolyte side reactions from the source, thereby inhibiting the acid byproducts from damaging the positive and negative electrode interface films and reducing the positive and negative electrode interface side reactions; the acid byproducts can also be used to inhibit the damage to the positive electrode active material and reduce the dissolution of transition metal ions at the positive electrode, and the carbon-carbon triple bond can be used to adsorb transition metal ions that may be dissolved from the positive electrode, thereby significantly reducing the deposition of transition metal ions at the negative electrode and significantly reducing the damage to the negative electrode SEI film by transition metal ions that may be dissolved from the positive electrode; the acid byproducts can also be used to inhibit the damage to the negative electrode SEI film, further improving the stability of the negative electrode SEI film and reducing the negative electrode interface side reactions.

[0137] In some embodiments, the following method can be used to test the D of the negative electrode active material or the positive electrode active material: v 50. D v 3. D v1, etc. Malvern 2000 (MasterSizer 2000) laser particle size analyzer was used, and the reference standard process was GB / T19077-2016 / ISO 13320:2009. The detailed test process included: taking an appropriate amount of the sample to be tested, adding a solvent (the solvent can be deionized water, and the sample concentration can be controlled at 8%~12% shading), and ultrasonic treatment for 5 min (53KHz / 120W) to fully disperse the sample, and then measuring the sample according to GB / T19077-2016 / ISO 13320:2009 standard. Non-limiting examples of solvents include deionized water and anhydrous ethanol. After the sample is poured into the injection tower, it circulates with the solution to the test optical path system. When the particles are irradiated by the laser beam, the particle size distribution characteristics of the particles can be obtained by receiving and measuring the energy distribution of the scattered light. A particle size volume distribution diagram is drawn based on the test data, and D is obtained from the distribution diagram. v 50 and other parameters. In order to avoid the influence of agglomeration in the drying process on the particle size test, the washed wet sample was taken for dispersion test.

[0138] The types and concentrations of inorganic components in the electrolyte (including electrolyte salts and inorganic additives) can be tested with reference to relevant standards such as GB / T 34672-2017 General Rules for Ion Chromatography of Chemical Reagents, JY / T020-1996 General Rules for Ion Chromatography Analysis Methods, and GB / T 6040-2019 General Rules for Infrared Spectroscopy Analysis Methods, and updated versions of standard methods can be preferred. The types and content tests of organic components in the electrolyte (including non-aqueous solvents and organic additives) can be tested with reference to relevant standards such as GB / T 9722-2023 General Rules for Gas Chromatography of Chemical Reagents.

[0139] In addition, those skilled in the art can also identify the components contained in the electrolyte of the lithium-ion secondary battery by one or more of the following detection methods, including but not limited to: nuclear magnetic resonance hydrogen spectroscopy ( 1 H NMR) method, high performance liquid chromatography (HPLC) method, matrix-assisted laser desorption-mass spectrometry (MADI-TOF) method, Fourier transform infrared spectroscopy (FT-IR) method, ultraviolet spectroscopy, gas chromatography (GC) method, etc. The sample preparation methods and test methods of these test methods are known to those skilled in the art, and the test parameters can be appropriately adjusted according to the structure of the material or substance and the sample characteristics. As a non-limiting example, FT-IR, ultraviolet spectroscopy, 1 The component types and contents of the electrolyte are detected by one or more methods such as H NMR, mass spectrometry, MADI-TOF, GC, etc., but are not limited thereto.

[0140] The sample of electrolyte to be tested can be obtained by disassembling the battery cell.

[0141] In the present application, the sample to be tested of the "positive electrode active material" in the positive electrode sheet of the lithium-ion secondary battery can be obtained by disassembling the battery, taking out the positive electrode sheet, and extracting the positive electrode active material from the positive electrode active layer of the positive electrode sheet by solvent washing, ultrasonic dispersion, centrifugal separation, graded sedimentation, sintering and other methods, and drying to obtain a powder sample. The obtained powder sample can be used for laser particle size analysis and testing, and can also be used for other tests. In addition, the powder material extracted from the positive electrode active layer can also be sintered to remove the organic components, thereby obtaining a powder sample of the positive electrode active material.

[0142] Exemplarily, the preparation of the powder sample of the positive electrode active material can be carried out by the following method: disassembling the battery, taking out the positive electrode plate, soaking and cleaning it with a solvent such as dimethyl carbonate to remove the residual electrolyte; scraping the powder material of the positive electrode active layer, using a solvent (such as N-methylpyrrolidone (NMP) etc.) to fully soak the powder material extracted from the positive electrode active layer, so that organic components such as binders are dissolved in the solvent (the dissolution can also be promoted by ultrasonic dispersion etc.), washing, filtering, collecting the solid phase, and then using the density difference to centrifuge to separate the relatively low-density conductive agent from the suspension, collecting the centrifugal precipitate to obtain the positive electrode active material to be tested.

[0143] The elemental composition of the positive electrode active material in the positive electrode active layer can be analyzed by methods known in the art, including but not limited to the following methods: inductively coupled plasma spectroscopy (ICP), X-ray diffraction (XRD), single crystal X-ray diffraction (SCXRD), energy dispersive spectrometer (EDS), etc. The sample preparation methods and test methods of these test methods are known to those skilled in the art, and the test parameters can be appropriately adjusted according to the characteristics of the sample. The ICP method can be used to perform quantitative test analysis of the content of the components in the positive electrode active material.

[0144] To detect the positive electrode active material in the positive electrode active layer, after the battery is fully discharged, the battery cell is disassembled, the positive electrode plate is taken out, the material of the positive electrode active layer is scraped, and the type and proportion of elements are tested and analyzed using elemental analysis methods such as inductively coupled plasma (ICP) spectroscopy, thereby confirming the elemental composition and chemical formula of the positive electrode active material.

[0145] In some embodiments, the D of the positive electrode active material v 3 is greater than or equal to 1μm, and can be selected as 1μm~2μm, and can be further selected as 1μm~1.6μm. It can also be any of the following values ​​or a range consisting of any two of the following values: 1μm, 1.1μm, 1.2μm, 1.4μm, 1.5μm, 1.6μm, 1.8μm, 2μm, etc.

[0146] By increasing the D v 3 Controlling within the aforementioned range is conducive to better controlling the content of small-sized particles with smaller particle size and larger specific surface area in the positive electrode active material, thereby better reducing the interfacial side reactions of the positive electrode, and can better be based on the multiple synergistic effects of the positive electrode active material and the first additive in the electrolyte, which is conducive to better significantly improving the high-temperature performance while also taking into account good room-temperature performance.

[0147] In some embodiments, the average particle size of the primary particles in the positive electrode active material is 1.1μm~3.0μm, and can be optionally 1.2μm~2.5μm, or can be any of the following values ​​or a range consisting of any two of the following values: 1.1μm, 1.2μm, 1.4μm, 1.5μm, 1.6μm, 1.8μm, 2μm, 2.2μm, 2.4μm, 2.5μm, 2.6μm, 2.8μm, 3.0μm, etc.

[0148] In this application, the “average particle size of primary particles in the positive electrode active material” may be denoted as D 1 .

[0149] In the present application, unless otherwise specified, the "average particle size of primary particles" in the positive electrode active material refers to the average particle size of each primary particle of the positive electrode active material. The "particle size of primary particles" refers to the maximum diameter of the primary particles in each direction.

[0150] In the present application, unless otherwise specified, the "primary particles" in the positive electrode active material are the basic units of particles in the positive electrode active material. It is understood that there are primary particles in the positive electrode active material. In the positive electrode active material, the primary particles can be in a non-agglomerated state or can be formed into aggregates by multiple primary particles. The non-agglomerated primary particles can be referred to as "non-agglomerated primary particles", and the aggregates formed by multiple primary particles can be referred to as "secondary particles".

[0151] By controlling the average particle size of the primary particles in the positive electrode active material (denoted as D1) within the aforementioned range, it is beneficial to make the primary particles in the positive electrode active material have a more suitable size, which can not only control the positive electrode active material to have a more suitable ion transmission path, but also better inhibit the positive electrode interface reaction, reduce the dissolution of transition metal ions and their damage to the negative electrode SEI film, and then control the negative electrode film formation consumption of acetylene base additives, thereby improving the cycle performance of lithium-ion secondary batteries and inhibiting the increase in battery internal resistance. Based on the synergy of the aforementioned effects, but not limited to the aforementioned theory, it is beneficial to better coordinate the control of the structural stability of the positive electrode active layer, the internal resistance of the battery and the consumption of acetylene base additives participating in the negative electrode film formation, which is beneficial to better significantly improve the high temperature performance while taking into account good room temperature performance.

[0152] The particle morphology of the positive electrode active material can be used to count the particle size of the primary particles in the positive electrode active material, and then obtain the average particle size of the primary particles in the positive electrode active material. The particle morphology of the positive electrode active material can be obtained by using a scanning electron microscope (such as ZEISS Sigma 300, JEOL scanning electron microscope, Axia ChemiSEM scanning electron microscope, etc.). The sample to be tested can be obtained by laying and sticking the powder sample of the positive electrode active material on a conductive adhesive, or by using the cross section of the positive electrode sheet for SEM testing. In a non-limiting manner, the SEM test can refer to JY / T(001)-1996. Randomly select one or more areas in the sample to be tested for scanning testing, and based on the SEM image at a certain magnification, count the particle size of each primary particle in the scanned area and the frequency of occurrence of different particle sizes, and then calculate and obtain the average particle size of each primary particle counted. In a non-limiting manner, the magnification of a single scanning area can be 1000X, but is not limited thereto. In order to improve the accuracy of the statistical results, multiple areas can be randomly selected for scanning. The number of primary particles counted may be hundreds, or may be greater than or equal to 1000, or may be greater than or equal to 2000. Increasing the number of primary particles counted is beneficial to improving the accuracy of the statistical results.

[0153] In the present application, unless otherwise specified, the maximum diameter of the primary particles in each direction in the SEM morphology of the positive electrode active material is recorded as the “particle size of the primary particles in the positive electrode active material”.

[0154] In some embodiments, a lithium-ion secondary battery is provided, which includes a positive electrode plate, a negative electrode plate and an electrolyte, wherein a separator is arranged between the positive electrode plate and the negative electrode plate; the positive electrode plate includes a positive electrode active layer, and the positive electrode active layer includes a positive electrode active material; the electrolyte includes an electrolyte salt, a non-aqueous solvent and an additive; the positive electrode active material includes a lithium transition metal oxide positive electrode material, and the average particle size of the primary particles in the positive electrode active material is 1.1 μm~3.0 μm (also refer to the appropriate numerical value or range in the context); the additive includes a first additive, and the first additive is an acetylene base additive containing a Lewis base nitrogen heterocycle.

[0155] For a high energy density battery system whose positive electrode active material contains a lithium transition metal oxide positive electrode material, by introducing a first additive containing a carbon-carbon triple bond and a Lewis base nitrogen heterocycle into the electrolyte, the high temperature performance of the battery can be significantly improved. Then, by controlling the average particle size (D1) of the primary particles of the positive electrode active material within a more moderate range (such as the average particle size of the primary particles in the positive electrode active material is 1.1μm~3.0μm), the positive electrode active material can be controlled to have a more suitable ion transmission path, and the positive electrode interface reaction can be better inhibited at the same time, reducing the dissolution of the positive electrode transition metal ions and their damage to the negative electrode SEI film, thereby controlling the negative electrode film formation consumption of the acetylene base additive, thereby improving the cycle performance of the lithium ion secondary battery and inhibiting the increase in the internal resistance of the battery; thus, through the aforementioned multiple synergistic effects, but not limited to the aforementioned mechanism, the high temperature performance can be significantly improved while significantly inhibiting the increase in interfacial impedance that may be caused by the first additive participating in the negative electrode film formation, thereby significantly improving the high temperature performance of the high energy density battery system while also having good room temperature performance.

[0156] In this application, D of the positive electrode active material is v 50 (can be recorded as D v 50 A ) relative to the average particle size of primary particles in the positive electrode active material (D 1 ) is recorded as B1. Then, B1=D v 50 A / D 1 .

[0157] In some embodiments, the positive electrode sheet satisfies one or more of the following characteristics:

[0158] (a1) D of positive electrode active material v 50 is 2.5 μm to 5 μm, and can be 3 μm to 4.5 μm, and can also be any of the following values ​​or a range consisting of any two of the following values: 2.5 μm, 2.6 μm, 2.8 μm, 3.0 μm, 3.2 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.8 μm, 4.0 μm, 4.2 μm, 4.4 μm, 4.5 μm, 4.6 μm, 4.8 μm, 5 μm, etc.;

[0159] (a2) B1 is 1 to 2.5, and can be 1.8 to 2.3, and can also be any of the following values ​​or a range consisting of any two of the following values: 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.8, 2.0, 2.1, 2.2, 2.3, etc.

[0160] In some embodiments, the positive electrode sheet satisfies one or more of the following characteristics:

[0161] (a1') D of positive electrode active material v 50 is 3 μm to 4.5 μm, and can also be any of the following values ​​or a range consisting of any two of the following values: 3 μm, 3.2 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.8 μm, 4.0 μm, 4.2 μm, 4.4 μm, 4.5 μm, etc.;

[0162] (a2') B1 is 1.8 to 2.3, and may be any one of the following values ​​or a range consisting of any two of the following values: 1.8, 2.0, 2.1, 2.2, 2.3, etc.

[0163] By increasing the D v 50 is controlled within the aforementioned range, which is conducive to making the positive electrode active material have a more suitable particle size distribution, and can indirectly adjust the contact area between the positive electrode active material and the electrolyte, which is conducive to better inhibiting the interface side reaction between the positive electrode active material and the electrolyte during the cycle and / or storage process, reducing the dissolution of the positive electrode transition metal ions, thereby better improving the cycle performance of the lithium ion secondary battery and inhibiting the increase of the battery internal resistance; it is also conducive to better controlling the ion transmission path of the positive electrode active material particles as a whole; based on the synergy of the aforementioned effects, but not limited to the aforementioned theory, it is conducive to better improving the high temperature performance while taking into account the good room temperature performance.

[0164] By increasing the D v When the ratio (B1) of 50 to the average particle size of the primary particles in the positive electrode active material is controlled within the aforementioned range, it is beneficial to make the median particle size of the positive electrode active material particles close to the average particle size of the primary particles as the basic unit of the particles, thereby reducing the agglomeration ratio of the primary particles in the positive electrode active material, reducing the content of the secondary particles as the primary particle agglomerates, and correspondingly increasing the proportion of non-agglomerated primary particles; compared with the secondary particles with primary particle interfaces, the non-agglomerated primary particles do not have primary particle interfaces in the secondary particles, so that the non-agglomerated primary particles can better resist the risk of particle cracking during the cycle and / or storage process; it is also beneficial to better control the ion transmission path of the positive electrode active material particles as a whole; by controlling B1 within the aforementioned range, the structural stability of the positive electrode active material can be better improved, which is more conducive to reducing the positive electrode interface side reactions and slowing down the electrolyte consumption, reducing the dissolution of the positive electrode transition metal ions, and is more conducive to improving the battery life and inhibiting the increase of the battery internal resistance, which is conducive to better improving the high temperature performance while taking into account the good room temperature performance.

[0165] In some embodiments, the D of the positive electrode active material v50 is 2.5μm~5μm, and can be 3μm~4.5μm, and can also be any of the following values ​​or a range consisting of any two of the following values: 2.5μm, 2.6μm, 2.8μm, 3.0μm, 3.2μm, 3.4μm, 3.5μm, 3.6μm, 3.8μm, 4.0μm, 4.2μm, 4.4μm, 4.5μm, 4.6μm, 4.8μm, 5μm, etc.; positive electrode The average particle size (D1) of the primary particles in the active material is 1.1μm~3.0μm, and can be optionally 1.2μm~2.5μm. It can also be any of the following values ​​or a range consisting of any two of the following values: 1.1μm, 1.2μm, 1.4μm, 1.5μm, 1.6μm, 1.8μm, 2μm, 2.2μm, 2.4μm, 2.5μm, 2.6μm, 2.8μm, 3.0μm, etc.

[0166] In some embodiments, B1 of the positive electrode active material is 1~2.5, and can be 1.8~2.3, or any of the following values ​​or a range consisting of any two of the following values: 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.8, 2.0, 2.1, 2.2, 2.3, etc.; the average particle size (D1) of the primary particles in the positive electrode active material is 1.1μm~3.0μm, and can be 1.2μm~2.5μm, or any of the following values ​​or a range consisting of any two of the following values: 1.1μm, 1.2μm, 1.4μm, 1.5μm, 1.6μm, 1.8μm, 2μm, 2.2μm, 2.4μm, 2.5μm, 2.6μm, 2.8μm, 3.0μm, etc.

[0167] By synergistically controlling the D v 50 (or B1) and the average particle size of the primary particles in the positive electrode active material are beneficial to taking into account the ion transmission path of the primary particles and the particles as a whole in the positive electrode active material, and at the same time better inhibiting the positive electrode interface side reaction. Based on the synergy of the aforementioned effects, but not limited to the aforementioned theory, it is beneficial to better control the internal resistance of the battery, and is beneficial to better take into account good room temperature performance while significantly improving the high temperature performance.

[0168] In some embodiments, the negative electrode sheet includes a negative electrode active layer, the negative electrode active layer includes a negative electrode active material; v 50 is 8μm~20μm, and can be optionally 10μm~20μm, and can be further optionally 10μm~18μm. It can also be any of the following values ​​or a range consisting of any two of the following values: 8μm, 8.5μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, etc.

[0169] By increasing the D v When 50 is controlled within the aforementioned range, the specific surface area of ​​the negative electrode active material can be controlled within a relatively low range, which is beneficial to reducing the negative electrode interface side reactions, reducing or delaying the negative electrode interface consumption of the first additive, and is also beneficial to better control the ion transmission path of the negative electrode active material particles as a whole. Based on the synergy of the aforementioned effects, but not limited to the aforementioned theory, it is beneficial to better control the internal resistance of the battery, and is beneficial to better improve the high temperature performance while taking into account good room temperature performance.

[0170] In the present application, the sample to be tested of the "negative electrode active material" in the negative electrode sheet of the lithium-ion secondary battery can be obtained by disassembling the battery, taking out the negative electrode sheet, extracting the negative electrode active material from the negative electrode active layer of the negative electrode sheet by solvent washing, ultrasonic dispersion, centrifugal separation, graded sedimentation, etc., and drying to obtain a powder sample. The obtained powder sample can be used for laser particle size analysis and testing, and can also be used for other tests.

[0171] In some embodiments, the D of the negative electrode active material v 1 is greater than or equal to 1.5 μm.

[0172] By controlling the D v 1 Within the aforementioned range, the negative electrode interface side reaction can be significantly inhibited, the consumption rate of the first additive can be reduced, and the battery internal resistance growth rate can be reduced.

[0173] In some embodiments, the specific surface area (BET) of the negative electrode active material is 0.5 m 2 / g~2.8m 2 / g, optional 0.5m 2 / g~2.0m 2 / g, further optional 0.7m 2 / g~1.6m 2 / g, can also be any of the following values ​​or a range consisting of any two of the following values: 0.5 m 2 / g, 0.6 m 2 / g, 0.7 m 2 / g, 0.8 m 2 / g, 1.0 m 2 / g, 1.2 m 2 / g, 1.4m 2 / g, 1.5 m 2 / g, 1.6 m 2 / g, 1.8 m 2 / g, 2.0 m 2 / g, 2.2 m 2 / g, 2.4 m2 / g, 2.5 m 2 / g, 2.6 m 2 / g, 2.8m 2 / g, etc.

[0174] In this application, unless otherwise specified, the "specific surface area" of the negative electrode active material has a well-known meaning in the art. It can be tested by nitrogen adsorption specific surface area analysis test method and calculated by BET (Brunauer Emmett Teller) method, wherein the nitrogen adsorption specific surface area analysis test can be performed by Tri Star II specific surface area and pore analyzer of Micromeritics Company of the United States, and the test steps can refer to GB / T 19587-2004. The detailed steps are as follows: nitrogen is used as the adsorption gas, and the specific surface area of ​​the material is calculated by the BET method; the sample to be tested is added into the BET test tube to meet the 2 / 3 of the bottom bulb, and the sample is degassed and heated; after cooling to room temperature, nitrogen is backfilled to remove the vacuum and the sample tube mouth is blocked with a bottle stopper, and the sample weight is recorded; the bottle stopper is removed, the filling rod is added, the sample tube is installed in the instrument analysis station, and the test is started after the sample weight is input. Before the test, the sample to be tested can be dried first.

[0175] In some embodiments, the negative electrode sheet includes a negative electrode active layer, and the negative electrode active layer includes a negative electrode active material; the negative electrode active material includes at least one of a carbon-based material and a silicon-based material. In some embodiments, the negative electrode active material includes a carbon-based material. Without limitation, the carbon-based material may include one or more of a graphite-based material, a soft carbon, and a hard carbon. The carbon-based material may include one or more of artificial graphite, natural graphite, soft carbon, and hard carbon. Without limitation, the mass proportion of the silicon-based material in the negative electrode active material may be 0-30%, optionally 1%-30%, further optionally 1%-25%, and may also be 0%-25%, and may also be any of the following percentages or a range selected from any two of the following percentages: 0, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 10%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, etc.

[0176] In some embodiments, the negative electrode active material includes a graphite-based material, and may further be a graphite-based material.

[0177] In the present application, "graphite-based material" refers to a negative electrode active material containing graphite, and the graphite-based material includes at least a graphite body. Without limitation, the graphite-based material may include one or more of a coated graphite-based material and an uncoated graphite. The coated graphite-based material includes a graphite body and a coating layer located at least on a portion of the surface of the graphite body. It is understood that the coating layer is different from the material in the graphite body. Without limitation, the mass proportion of the graphite body in the graphite-based material may be 90% to 100%, or may be any of the following percentages or a range selected from any two of the following percentages: 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%. The graphite-based material may include, but is not limited to, one or more of artificial graphite and natural graphite. In some embodiments, the carbon-based material is a graphite-based material. In some embodiments, the negative electrode active material is a graphite-based material.

[0178] In the present application, a "graphite body" consists of graphite.

[0179] In some embodiments, the mass proportion of graphite-based materials in the negative electrode active material is 70%~100%, further optionally 75%~100%, further optionally 80%~100%, further optionally 90%~100%, further optionally 95%~100%, further optionally 97%~100%, and can also be any of the following percentages or a range consisting of any two of the following percentages: 70%, 75%, 80%, 85%, 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.

[0180] In some embodiments, the negative electrode active material includes a carbon-based material. In a non-limiting manner, the mass proportion of the carbon-based material in the negative electrode active material is 70% to 100%, optionally 70% to 99%, further optionally 75% to 99%, further 75% to 100%, further 80% to 100%, further 90% to 100%, and any of the following percentages or a range selected from any two of the following percentages: 70%, 75%, 80%, 85%, 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.

[0181] In some embodiments, the negative electrode active material includes graphite, and further, the graphite may include one or more of artificial graphite and natural graphite.

[0182] Without limitation, the mass proportion of silicon-based materials in the negative electrode active material can be 0% to 30%, optionally 0% to 25%, or any of the following percentages or a range consisting of any two of the following percentages: 0, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 10%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, etc.

[0183] In some embodiments, the negative electrode active material includes a silicon-based material. Without limitation, the silicon-based material may include one or more of elemental silicon, silicon-oxygen compounds, silicon-carbon composite materials, silicon-nitrogen composite materials, and silicon alloys. Without limitation, the mass proportion of silicon-based materials in the negative electrode active material may be 1% to 30%, optionally 1% to 25%, or any of the following percentages or a range selected from any two of the following percentages: 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 10%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, etc.

[0184] "Silicon-carbon composite material" is a silicon-based material, which includes a porous carbon matrix and elemental silicon located in the pores of the porous carbon matrix. The silicon-carbon composite material can be obtained by a vapor deposition method. Those skilled in the art can prepare the silicon-carbon composite material by conventional methods in the art.

[0185] In some embodiments, the negative electrode sheet includes a negative electrode active layer, the negative electrode active layer includes a negative electrode active material; the negative electrode active material includes at least one of a carbon-based material and a silicon-based material;

[0186] The negative electrode sheet meets one or more of the following characteristics:

[0187] (b1) the mass proportion of the silicon-based material in the negative electrode active material is 0-30%, and can be 1%-30% (also refer to the appropriate numerical value or range in any embodiment above and below);

[0188] (b2) The silicon-based material includes a silicon-carbon composite material, which includes a porous carbon matrix and elemental silicon located in the pores of the porous carbon matrix; without limitation, the mass proportion of the silicon-carbon composite material in the silicon-based material can be 80% to 100%, optionally 90% to 100%, or any of the following percentages or a range consisting of any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.

[0189] By controlling the content and / or type of silicon-based materials in the negative electrode active material within the aforementioned range, it is beneficial to better control the expansion and contraction changes of the negative electrode, reduce the generation of fresh interfaces, inhibit negative electrode interface side reactions, reduce the consumption rate of the first additive, reduce the growth rate of battery internal resistance, and improve the battery life. For example, among silicon-based materials, the volume expansion and contraction changes of silicon-carbon composite materials are relatively low.

[0190] In some embodiments, the positive electrode active material includes a positive electrode active body and a coating layer located on the positive electrode active body.

[0191] For positive electrode active materials or negative electrode active materials including a coating layer (an example of a coating layer is a carbon coating layer), the cross-section can be cut using FIB (focused ion beam) and the particle cross-sectional morphology can be observed under TEM (transmission electron microscope). A clear boundary can be observed at the coating interface, and the thickness and average thickness of the coating layer can be analyzed and calculated based on the TEM image. Further combined with one or more methods such as energy dispersive spectroscopy (EDS) analysis and Raman spectroscopy, the types of substances in the coating layer and the positive electrode active body can be confirmed, or the types of substances in the coating layer and the negative electrode active body can be confirmed.

[0192] Those skilled in the art can identify the components in the positive electrode active layer and the negative electrode active layer by one or more of the following detection methods known in the art, including but not limited to: Fourier transform infrared (FT-IR) spectroscopy, ultraviolet spectroscopy, nuclear magnetic resonance spectroscopy (HNMR), 1 H NMR) method, gel permeation chromatography (GPC) method, high performance liquid chromatography (HPLC) method, mass spectrometry, X-ray photoelectron spectroscopy (XPS) method, X-ray diffraction (XRD) method, Raman spectroscopy (Raman) method, single crystal X-ray diffraction (SCXRD) method, inductively coupled plasma spectroscopy (ICP) method, energy dispersive spectrometer (EDS) analysis, etc. The sample preparation methods and test methods of these test methods are known to those skilled in the art, and the test parameters can be appropriately adjusted according to the structure of the material or substance and the sample characteristics.

[0193] As a non-limiting example, EDS can be used to distinguish carbon elements from silicon elements, and then distinguish carbon-based materials from silicon-based materials. For another example, EDS can be used to detect the type and content of the conductive agent, but is not limited thereto.

[0194] Taking the negative electrode active material including natural graphite and artificial graphite as a non-limiting example, natural graphite and artificial graphite can be distinguished by the appearance morphology of the particles; X-ray diffraction (XRD) analysis test can be further performed. In the XRD spectrum, if the characteristic peak near 2θ 26.5° is very sharp and has a high intensity, it is natural graphite; if the characteristic peak near 2θ 26.5° is relatively wide and has a weak intensity, it is artificial graphite.

[0195] Taking the negative electrode active materials including graphite and soft carbon as an example, Raman spectroscopy can be used to distinguish graphite and soft carbon; in more detail, the characteristic peak information of the carbon component in the spectrum (such as the intensity ratio of D peak / G peak, I D / G ) to analyze soft carbon. Both D peak and G peak are Raman characteristic peaks of carbon atom crystal. D peak represents the defects of carbon atom crystal. The more defects there are, the greater the intensity of D peak is. The intensity of D peak can reflect the content of amorphous (turbostratified stacking) area. G peak represents the in-plane stretching vibration of sp2 hybridization of carbon atoms. The intensity of G peak can reflect the content of graphitized (layered structure) area. As the degree of disorder of carbon atoms increases, the intensity ratio of D peak to G peak also increases. You can also compare Raman spectra I D / G Standard Raman spectrum of graphite I D / G The difference between the D peak and the G peak of the Raman spectrum can be used to distinguish between graphite and hard carbon. Similarly, the difference between the D peak and the G peak of the Raman spectrum can be used to distinguish between natural graphite and artificial graphite.

[0196] In some embodiments, the mass percentage of the first additive in the electrolyte is less than 3.6%.

[0197] In some embodiments, the mass percentage of the first additive in the electrolyte is 0.02% to 3.6%.

[0198] In some embodiments, the mass percentage of the first additive in the electrolyte is 0.02% to 2%.

[0199] In some embodiments, the mass percentage of the first additive in the electrolyte is 0.1% to 1.6%, and can be optionally 0.1% to 1.2%.

[0200] Without limitation, the mass percentage of the first additive in the electrolyte can also be any of the following percentages or a range consisting of any two of the following percentages: 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 3%, 3.2%, etc.

[0201] By controlling the mass proportion of the first additive in the electrolyte within the aforementioned range, the first additive can continue to play a role in repairing the SEI film during circulation and / or storage, which is more conducive to significantly improving high-temperature performance while also taking into account good room-temperature performance.

[0202] In some embodiments, the additive includes a negative electrode film-forming additive different from the first additive.

[0203] "Negative electrode film-forming additive" refers to an additive that can decompose and participate in the formation of the negative electrode SEI film at the negative electrode working potential. The higher the reduction potential of the negative electrode film-forming additive, that is, the more positive the potential value relative to Li / Li⁺, the earlier the negative electrode film-forming additive decomposes, and then participates in the formation of the negative electrode SEI film. It is understandable that some negative electrode film-forming additives can also participate in the formation of the interface film (CEI film) at the positive electrode. Generally, those skilled in the art can judge whether a certain additive can participate in the formation of the negative electrode SEI film based on methods such as reduction potential analysis, decomposition product and SEI film component analysis, and electrochemical performance verification; exemplarily, the reduction potential of the additive can be measured by cyclic voltammetry in a simulated battery environment (such as lithium metal to the working electrode); exemplarily, the SEI film composition can be analyzed by chemical composition analysis methods including but not limited to X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR) and the like; exemplarily, it can be judged whether a certain additive introduced can participate in the formation of the negative electrode SEI film based on the changes in performance indicators such as the first coulomb efficiency, cycle stability and impedance spectrum when the additive is introduced or not.

[0204] The negative electrode film-forming additive different from the first additive can competitively participate in the negative electrode film formation, can reduce or delay the negative electrode film formation consumption of the first additive, and can inhibit the increase in the negative electrode interface impedance caused by the participation of the first additive in the negative electrode film formation, which is conducive to better improving the high temperature performance of the high energy density battery system while also having good room temperature performance.

[0205] In some embodiments, the additive includes one or more of a second additive, a third additive, and a fourth additive.

[0206] Without limitation, the sum of the mass proportions of the second additive, the third additive and the fourth additive in the electrolyte may be greater than or equal to 0.02%, optionally 0.02% to 5%, further optionally 0.02% to 3%, further optionally 0.02% to 1.5%.

[0207] In some embodiments, the second additive is one or more of a silane additive and a siloxane additive.

[0208] Without limitation, the second additive may include tris(trimethylsilyl)borate (TMSB).

[0209] Without limitation, the silane-based additive may include tris(trimethylsilyl)borate (TMSB).

[0210] In some embodiments, the third additive is one or more of an isocyanate additive and an anhydride additive.

[0211] In some embodiments, the fourth additive is one or more of a lithium salt additive and a phosphate ester additive.

[0212] Without limitation, the isocyanate additive may include, but is not limited to, toluene diisocyanate.

[0213] Without limitation, the anhydride additive may include one or more of maleic anhydride, citraconic anhydride, trifluoromethylmaleic anhydride, succinic anhydride, glutaric anhydride, succinic anhydride, and the like.

[0214] Without limitation, the mass proportion of the anhydride additive in the electrolyte may be 0% to 1%, optionally 0.01% to 1%, and further optionally 0.1% to 1%.

[0215] Without limitation, the lithium salt additive may include one or more of oxalate lithium salts, lithium tetrafluoroborate, lithium difluorophosphate, fluorosulfonic acid lithium salts, etc.; without limitation, oxalate lithium salts may include one or more of lithium difluorooxalatoborate, lithium difluorodioxalatophosphate, lithium tetrafluorooxalatophosphate, etc.; without limitation, fluorosulfonic acid lithium salts may include one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide (LiFSI), etc.

[0216] Without limitation, the phosphate additive may include a silicon-based phosphate additive; without limitation, the silicon-based phosphate additive may include one or more of tris(trimethylsilyl)phosphate, tris(trimethylsilyl)phosphite, and the like.

[0217] In some embodiments, the additive includes a lithium salt additive.

[0218] Without limitation, the mass proportion of the lithium salt additive in the electrolyte may be 0-3%, may be greater than 0 and less than or equal to 3%, and may further be 0.05%-3%.

[0219] In the present application, when the mass percentage of the lithium salt additive (such as LiFSI) in the electrolyte is greater than 3%, the mass percentage of the lithium salt additive (such as LiFSI) in the second additive in the electrolyte is recorded as 3%.

[0220] In some embodiments, the additive includes a phosphate-based additive.

[0221] Without limitation, the mass proportion of the phosphate additive in the electrolyte may be 0-2%, may be greater than 0 and less than or equal to 2%, and may further be 0.1%-2%.

[0222] In some embodiments, the mass percentage of the second additive in the electrolyte is 0% to 1%, and may be 0.1% to 1%.

[0223] In some embodiments, in the electrolyte, the mass ratio of the second additive to the first additive is 0.1~50, can be 0.2~50, further can be 0.3~50, further can be 0.3~20, can also be 0.2~1, can be 0.2~0.5, can also be any of the following values ​​or a range consisting of any two of the following values: 0.1, 0.2, 0.4, 0.5, 0.6, 0.8, 1, 2, 3, 4, 5, 6, 8, 10, 15, 20, 25, 30, 35, 40, 45, 50, etc.

[0224] In some embodiments, the mass percentage of the third additive in the electrolyte is 0% to 1%, and may be 0.1% to 1%.

[0225] In some embodiments, in the electrolyte, the mass ratio of the third additive to the first additive is 0.01~50, can be 0.1~50, further can be 0.2~50, further can be 0.3~50, further can be 0.3~20, can also be 0.01~1, can be 0.01~0.5, further can be 0.01~0.3, can also be any of the following values ​​or a range consisting of any two of the following values: 0.01, 0.02, 0.04, 0.05, 0.06, 0.08, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.8, 1, 2, 3, 4, 5, 6, 8, 10, 15, 20, 25, 30, 35, 40, 45, 50, etc.

[0226] In some embodiments, the mass percentage of the fourth additive in the electrolyte is 0% to 2%, and can be optionally 0.1% to 2%.

[0227] In some embodiments, in the electrolyte, the mass ratio of the fourth additive to the first additive is 0.1~100, which can be optionally 0.2~100, further optionally 0.2~50, further optionally 0.3~50, further optionally 0.3~20, and can also be 0.2~1, and can also be 0.08~100, can be optionally 0.08~50, further optionally 0.08~20, and can also be any of the following values ​​or a range consisting of any two of the following values: 0.05, 0.08, 0.1, 0.2, 0.4, 0.5, 0.6, 0.8, 1, 2, 3, 4, 5, 6, 8, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, etc.

[0228] In some embodiments, in the electrolyte, the mass ratio of the second additive, the third additive, the fourth additive and the first additive is (0-20): (0-20): (0:50): 1, which can also be combined with the features of any appropriate embodiment in the context. For example, in the electrolyte, the mass ratio of the second additive, the third additive, the fourth additive and the first additive can be (0.1-20): (0-20): (0:50): 1, can also be (0-20): (0.1-20): (0:50): 1, can also be (0-20): (0.1-20): (0.1:50): 1, can also be (0-0.5): (0-0.5): (0-1): 1, can also be (0.2-0.5): (0.01-0.5): (0.2-1): 1, etc.

[0229] The second additive, the third additive and the fourth additive can all be used as negative electrode film-forming additives. The second additive is a type of additive with low negative electrode film-forming impedance and a certain acid removal effect. Its acid removal effect is lower than that of the first additive, and its negative electrode film-forming impedance is lower than that of the first additive. The third additive is a type of additive with a good acid removal effect. Its acid removal effect is better than that of the first additive, but its negative electrode film-forming impedance is higher than that of the first additive. The negative electrode film-forming impedance of the fourth additive is very low, much lower than that of the first additive.

[0230] Utilizing the synergistic effect of the first additive and one or more of the second additive, the third additive and the fourth additive is beneficial to better improve the high temperature performance while also taking into account good room temperature performance.

[0231] In some embodiments, the electrolyte satisfies one or more of the following characteristics:

[0232] (c1) the molecular weight of the first additive is less than or equal to 500 Da;

[0233] (c2) the first additive contains 1 to 4 carbon-carbon triple bonds in the molecule; without limitation, the number of carbon-carbon triple bonds in the molecule of the first additive may be 1, 2, 3 or 4;

[0234] (c3) The carbon-carbon triple bond is CH≡C-;

[0235] (c4) the first additive contains 1 to 4 Lewis base nitrogen heterocycles in the molecule. Without limitation, the number of Lewis base nitrogen heterocycles in the first additive may be 1, 2, 3 or 4;

[0236] (c5) Lewis base nitrogen heterocycles including imidazole rings;

[0237] (c6) In the molecule of the first additive, the carbon-carbon triple bond and the Lewis base nitrogen heterocyclic ring are connected by a linker L 1 Connected, connecting base L 1 Contains C covalently bonded to a carbon-carbon triple bond 1-3 Alkylene or containing a fluorinated C covalently bonded to a carbon-carbon triple bond 1-3 Alkylene.

[0238] In some embodiments, the first additive satisfies one or more of the following characteristics:

[0239] (d1) the molecular weight of the first additive is less than or equal to 300 Da;

[0240] (d2) the first additive contains 1 to 4 imidazole rings in the molecule. Without limitation, the number of imidazole rings in the first additive may be 1, 2, 3 or 4;

[0241] (d3) Linking group L 1 Contains C covalently bonded to a carbon-carbon triple bond 1-3 Alkylene;

[0242] (d4) Lewis base nitrogen heterocycles include imidazole rings; the imidazole rings in the Lewis base nitrogen heterocycles are substituted by 0, 1 or more substituent groups Q 2 Substituted, the substituent group Q in the substituted imidazole group 2 Each independently is C 1-3 an alkyl group, a cyano group or a fluorine atom.

[0243] In some embodiments, the first additive is composed of a carbon-carbon triple bond, a C 1-3 Alkylene and -OC(=O)-R 10 Sequentially covalently bonded, R 10 It is a Lewis base nitrogen heterocycle.

[0244] In some embodiments, the first additive includes a compound II having a structure as shown in formula (II): Among them, L 11 C 1-3 Alkylene, Q 2 Independently for C 1-3 Alkyl, cyano or fluorine atom, p2 is 0, 1, 2 or 3;

[0245] Without limitation, the mass proportion of compound II in the first additive can be 80% to 100%, optionally 90% to 100%, or any of the following percentages or a range consisting of any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.

[0246] In this application, the term “C 1-3 "Alkylene", unless otherwise specified, may be methylene, ethylene or propylene, and may further be methylene, 1,2-ethylene or 1,3-propylene.

[0247] In this application, the term “C 1-3 "Alkyl", unless otherwise specified, may be methyl, ethyl or propyl, and may further be methyl, ethyl, n-propyl or isopropyl.

[0248] In some embodiments, L 11 For methylene.

[0249] In some embodiments, p2 is 0.

[0250] In some embodiments, Compound II is (Compound IIa).

[0251] Without limitation, the mass proportion of compound IIa in the first additive can be 80% to 100%, optionally 90% to 100%, or any of the following percentages or a range consisting of any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.

[0252] By controlling the molecular weight of the first additive within the aforementioned lower range, the first additive can have a smaller molecular size, which is beneficial for better controlling the low viscosity characteristics of the electrolyte, making the electrolyte have a higher conductivity, and better controlling the internal resistance of the battery.

[0253] By controlling the number of carbon-carbon triple bonds in the first additive within the aforementioned range, it is beneficial to suppress the increase in interfacial impedance caused by the first additive participating in the formation and repair of the SEI film, and it is also beneficial to control the influence of the first additive on the liquid phase impedance; thereby, the increase in battery internal resistance can be better suppressed.

[0254] By controlling the amount of the Lewis base nitrogen heterocycle in the first additive within the aforementioned range, it is beneficial to better absorb the acid byproducts in the electrolyte, and it is also beneficial to control the steric effect of the Lewis base nitrogen heterocycle on the carbon-carbon triple bond.

[0255] An example of a Lewis base nitrogen heterocycle is the imidazole ring in compound II.

[0256] In some embodiments, the additive in the electrolyte includes a cyclic sulfate ester.

[0257] Without limitation, the mass proportion of the cyclic sulfate in the electrolyte may be 0-3%, and may be optionally 0.1%-3%.

[0258] In the present application, "cyclic sulfate" contains one or more monocyclic sulfate units, and "monocyclic sulfate units" contain *-OS(=O) 2 -O-*, two *s each independently represent a bonding site to a carbon atom.

[0259] In some embodiments, the additive includes a polycyclic sulfate, which contains multiple monocyclic sulfate units.

[0260] In some embodiments, multiple monocyclic sulfate units in the polycyclic sulfate are linked in a chain-like manner.

[0261] In some embodiments, the number of monocyclic sulfate units in the polycyclic sulfate is 2 to 4, and further can be 2, 3 or 4.

[0262] In some embodiments, the monocyclic sulfate ester unit is a 5- to 7-membered monocyclic ring, which may be a 5-membered ring, a 6-membered ring or a 7-membered ring, and may further be a 5-membered ring or a 6-membered ring.

[0263] In some embodiments, the monocyclic sulfate unit is substituted with 0, 1 or more substituent groups Q 3 Substituted, the substituent group Q in the monocyclic sulfate unit 3 are independently halogen, C 1-3 Alkyl or C 1-3 Alternatively, the substituent group Q in the monocyclic sulfate unit 3 Each is independently a fluorine atom, a methyl group or a methoxy group.

[0264] By introducing cyclic sulfate into the electrolyte, the negative electrode interface film can be optimized, the stability of the negative electrode SEI film can be improved, the negative electrode interface side reactions can be reduced, and the negative electrode interface impedance and battery internal resistance can be better controlled.

[0265] In some embodiments, the additive in the electrolyte includes a fluorocarbonate additive.

[0266] Without limitation, the mass proportion of the fluorocarbonate additive in the electrolyte may be 0-10%, and may be optionally 0.1%-10%.

[0267] In some embodiments, the fluorinated carbonate additive may include fluorinated ethylene carbonate (FEC). Without limitation, the mass proportion of FEC in the electrolyte may be 0-10%, optionally 0-5%, further 0.1%-10%, and further optionally 0.1%-5%.

[0268] Fluoroethylene carbonate (FEC) can form a relatively strong interface film with lower ion transfer impedance on the surface of the negative electrode at room temperature. By introducing fluorocarbonate additives (such as FEC) into the electrolyte, it is helpful to reduce or delay the consumption of the first additive in the negative electrode film formation, and better control the negative electrode interface impedance and battery internal resistance.

[0269] In some embodiments, the electrolyte includes one or both of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and in some embodiments, the electrolyte includes at least lithium hexafluorophosphate.

[0270] In some embodiments, the molar volume concentration of lithium hexafluorophosphate in the electrolyte can be 0.5 mol / L ~1.2 mol / L, optionally 0.6 mol / L ~1.2 mol / L, optionally 0.7 mol / L ~1.2 mol / L, or any of the following concentrations or a range consisting of any two of the following concentrations: 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, etc.

[0271] In some embodiments, the electrolyte includes lithium bis(fluorosulfonyl)imide (LiFSI), which can act as a film-forming additive and also as an electrolyte salt in the electrolyte. In a non-limiting manner, the molar volume concentration of lithium bis(fluorosulfonyl)imide in the electrolyte can be 0.01 mol / L to 0.5 mol / L, optionally 0.01 mol / L to 0.3 mol / L, or any of the following concentrations or a range consisting of any two of the following concentrations: 0.01 mol / L, 0.02 mol / L, 0.025 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.075 mol / L, 0.08 mol / L, 0.09 mol / L, 0.1 mol / L, 0.12 mol / L, 0.14 mol / L, 0.15 mol / L, 0.16 mol / L, 0.18 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, 0.5mol / L, etc.

[0272] In some embodiments, the electrolyte includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide. Without limitation, the molar volume concentration of lithium bis(fluorosulfonyl)imide in the electrolyte can be greater than 0 mol / L and less than or equal to 0.5 mol / L, and can be selected from 0.01 mol / L to 0.5 mol / L, and can also be selected from a suitable range or value in any embodiment of the context.

[0273] Lithium bis(fluorosulfonyl)imide (LiFSI) can participate in the formation of a stable solid electrolyte interface film at the positive and negative electrodes. On the one hand, by introducing LiFSI into the electrolyte, the stability of the positive and negative electrode interface films can be improved; on the other hand, LiFSI's ability to dissociate lithium ions is better than lithium hexafluorophosphate (LiPF6), so the addition of LiFSI is also beneficial to improve the liquid phase conductivity.

[0274] In some embodiments, the negative electrode active material includes a coated negative electrode material, and the coated negative electrode material includes a negative electrode active body and a carbon coating layer located at least in part of the negative electrode active body. It is understood that the carbon coating layer has a different chemical composition from the negative electrode active body. The negative electrode active body can select at least one material suitable for negative electrode active materials known in the art. Without limitation, the negative electrode active body can include one or more of graphite and silicon-based materials; without limitation, graphite can include one or more of natural graphite and artificial graphite; without limitation, the silicon-based material can include one or more of elemental silicon, silicon oxide, silicon-carbon composite material, silicon-nitrogen composite material and silicon alloy. Without limitation, the carbon coating layer in the coated negative electrode material can include one or more of soft carbon, hard carbon and amorphous carbon. Without limitation, the average thickness of the carbon coating in the coated negative electrode material can be 1nm~500nm, optionally 100nm~500nm, and further optionally 100nm~200nm. In a non-limiting manner, the mass percentage of the coating layer in the coated active material is 0.2% to 5%, and may be 0.5% to 3%.

[0275] "Soft carbon" and "hard carbon" have well-known meanings in the art. Soft carbon can be graphitized after further high-temperature treatment, while hard carbon is difficult to graphitize even after further high-temperature treatment. In this application, unless otherwise specified, "amorphous carbon" refers to a transitional carbon material with a very low degree of graphitization crystallization and a nearly amorphous form (or without a fixed shape and periodic structural regularity).

[0276] In some embodiments, the carbon coating layer in the coated negative electrode material is one of a soft carbon coating layer, a hard carbon coating layer and an amorphous carbon coating layer. It can be understood that the material composition of the soft carbon coating layer is mainly soft carbon, the material composition of the hard carbon coating layer is mainly hard carbon, and the material composition of the amorphous carbon coating layer is mainly amorphous carbon.

[0277] In some embodiments, the negative electrode active material includes a coated negative electrode material, the coated negative electrode material includes a negative electrode active body and a carbon coating layer located at least in part of the negative electrode active body, the negative electrode active material D v 50 is 5μm~14μm, and can also be any of the following values ​​or a range consisting of any two of the following values: 5μm, 5.5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, etc.

[0278] In some embodiments, the negative electrode active material includes a coated negative electrode material, the coated negative electrode material includes a negative electrode active body and a carbon coating layer located at at least a portion of the negative electrode active body, the average particle size of the primary particles in the negative electrode active material is 0.1μm~1.6μm, and can also be any of the following values ​​or a range selected from any two of the following values: 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.4μm, 1.5μm, 1.6μm, etc.

[0279] In some embodiments, the negative electrode plate satisfies one or more of the following characteristics:

[0280] (a1) The mass proportion of the coated negative electrode material in the negative electrode active material can be 80% to 100%, optionally 90% to 100%, further optionally 92% to 100%, further optionally 95% to 100%, further optionally 95% to 98%, and can also be any of the following percentages or a range consisting of any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 92%, 94%, 95%, 96%, 98%, 100%, etc.;

[0281] (a2) The coated negative electrode material includes coated graphite, and the negative electrode active body in the coated graphite includes a graphite body. Without limitation, the mass proportion of the coated graphite in the negative electrode active material can be 80% to 100%, optionally 90% to 100%, further optionally 92% to 100%, further optionally 95% to 100%, further optionally 95% to 98%, and can also be any of the following percentages or a range consisting of any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 92%, 94%, 95%, 96%, 98%, 100%, etc.

[0282] In the present application, "coated graphite" is a coated negative electrode material, in which the negative electrode active body includes a graphite body; the coated graphite includes a graphite body and a carbon coating layer located on at least a portion of the surface of the graphite body.

[0283] In the present application, a "graphite body" consists of graphite.

[0284] By providing a coated negative electrode material (such as coated graphite) including a carbon coating layer in the negative electrode active material, the lithium ion transmission channel on the surface of the negative electrode active material can be optimized, lithium ion transmission can be promoted, and the kinetics of the lithium ion secondary battery can be improved. At the same time, it is also beneficial to inhibit the negative electrode interface side reactions and inhibit the increase in negative electrode interface impedance caused by the first additive participating in the negative electrode film formation.

[0285] In some embodiments, the coated negative electrode material is coated graphite, and the negative electrode active body is a graphite body.

[0286] In some embodiments, the non-aqueous solvent includes a linear carbonate.

[0287] In the present application, unless otherwise specified, "chain carbonate" refers to a chain compound having a *-OC(=O)-O-* structure, where two *s each independently represent a bonding site to a carbon atom.

[0288] In some embodiments, the structure of the linear carbonate is R 21 -OC(=O)-OR 22 , R 21 and R 22 Each is independently a chain alkyl group having 1 to 3 (can be 1, 2 or 3) carbon atoms. 21 and R 22 Each is independently methyl, ethyl or propyl. 21 and R 22 Each is independently methyl or ethyl.

[0289] In some embodiments, the non-aqueous solvent includes dimethyl carbonate. Without limitation, the mass proportion of dimethyl carbonate in the non-aqueous solvent is greater than or equal to 20%, optionally 20% to 50%, and further optionally 20% to 40%.

[0290] In some embodiments, the non-aqueous solvent includes a chain carboxylate compound. In a non-limiting manner, the mass proportion of the chain carboxylate compound in the non-aqueous solvent may be 0% to 40%.

[0291] In this application, unless otherwise specified, "chain carboxylate" refers to a chain compound having a *-C(=O)-O-* structure, where two *s each independently represent a bonding site with a carbon atom. Chain carboxylate compounds used in electrolytes for lithium-ion secondary batteries generally have a lower viscosity, which is beneficial to improving the lithium ion conductivity of the electrolyte.

[0292] In some embodiments, the non-aqueous solvent includes dimethyl carbonate. Without limitation, the mass proportion of dimethyl carbonate in the non-aqueous solvent may be 0% to 50%.

[0293] In some embodiments, the ionic conductivity of the electrolyte at 25°C is greater than or equal to 8 mS / cm, and can be 8 mS / cm to 20 mS / cm, further can be 9 mS / cm to 18 mS / cm, and can also be any of the following conductivities or a range consisting of any two of the following conductivities: 8 mS / cm, 9 mS / cm, 10 mS / cm, 11 mS / cm, 12 mS / cm, 13 mS / cm, 14 mS / cm, 15 mS / cm, 16 mS / cm, 18 mS / cm, 20 mS / cm, etc.

[0294] In this application, unless otherwise specified, the "ionic conductivity" of the electrolyte has a well-known meaning in the art, and can be tested and analyzed using existing methods in the art. The ionic conductivity can be obtained by testing with a conductivity tester, such as a DDSJ-318 conductivity meter. The test temperature can be 25±0.1°C. The test can be performed with reference to the method of HG / T 4067-2015. Unless otherwise specified, the unit of the ionic conductivity of the electrolyte is millisiemens / cm (mS / cm).

[0295] Unless otherwise specified, the following steps may be used for testing:

[0296] Pretreatment: Take the standard liquid and keep it at a constant temperature of 25℃ (deviation ±0.1℃), and take the test liquid and keep it at a constant temperature of the test temperature (deviation ±0.1℃);

[0297] Test: Test the instrument with two standard solutions at 25°C. After calibration, clean the electrode and place the test sample electrode vertically into the liquid to be tested. Click to start the test and wait for the data to stabilize for more than 10 seconds to record the test results.

[0298] In some embodiments, the lithium transition metal oxide-based cathode material has a layered crystal structure.

[0299] Without limitation, the mass proportion of lithium transition metal oxide positive electrode materials in the positive electrode active material is 80% to 100%, optionally 90% to 100%, further optionally 95% to 100%, and can also be any of the following percentages or a range selected from any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.

[0300] In some embodiments, the lithium transition metal oxide-based cathode material includes a lithium nickel-based oxide-based cathode material.

[0301] In this application, unless otherwise specified, "lithium nickel-based oxide positive electrode material" refers to a lithium transition metal oxide positive electrode material containing nickel. It is understood that the lithium nickel-based oxide positive electrode material includes lithium, non-lithium metal elements and oxygen elements; the non-lithium metal elements include nickel. Without limitation, the mass proportion of lithium nickel-based oxide positive electrode materials in the positive electrode active material is 80% to 100%, which can be 90% to 100%, and further can be 95% to 100%. It can also be any of the following percentages or a range selected from any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.

[0302] Examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and modified compounds thereof. Non-limiting examples of lithium cobalt oxides may include LiCoO 2 Non-limiting examples of lithium nickel oxides may include LiNiO 2 Non-limiting examples of lithium manganese oxides may include LiMnO 2 、LiMn 2 O 4 etc.; Non-limiting examples of lithium nickel cobalt manganese oxides may include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (Also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O 2 (Also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O 2 (Also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O 2 (Also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O 2 (Also referred to as NCM 811 ) etc. Non-limiting examples of lithium nickel cobalt aluminum oxide may include LiNi 0.80 Co 0.15 Al0.05 O 2 .

[0303] In some embodiments, the lithium transition metal oxide-based cathode material includes a lithium nickel cobalt-based oxide-based cathode material.

[0304] In some embodiments, the positive electrode active material includes a lithium nickel cobalt-based oxide positive electrode material. In a non-limiting manner, the mass proportion of the lithium nickel cobalt-based oxide positive electrode material in the positive electrode active material is 80% to 100%, optionally 90% to 100%, further optionally 95% to 100%, and can also be any of the following percentages or a range selected from any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.

[0305] "Lithium nickel cobalt-based oxide positive electrode material" refers to a lithium transition metal oxide positive electrode material containing nickel and cobalt elements, and is also a lithium nickel-based oxide positive electrode material containing cobalt elements. It can be understood that in this application, "lithium nickel cobalt-based oxide positive electrode material" includes lithium (Li), nickel (Ni), cobalt (Co) and oxygen (O).

[0306] In some embodiments, the lithium nickel cobalt-based oxide positive electrode material may further include an M2 element, which may be a manganese (Mn) element or an aluminum (Al) element. When the M2 element is manganese (Mn), the lithium nickel cobalt-based oxide positive electrode material is a lithium nickel cobalt manganese-based oxide positive electrode material, which may be recorded as an NCM-based positive electrode material, and when the M2 element is aluminum (Al), the lithium nickel cobalt-based oxide positive electrode material is a lithium nickel cobalt aluminum-based oxide positive electrode material, which may be recorded as an NCA-based positive electrode material.

[0307] In some embodiments, the positive electrode active material includes a lithium nickel cobalt manganese based oxide type positive electrode material.

[0308] In this application, unless otherwise specified, "lithium nickel cobalt manganese-based oxide positive electrode material" refers to a lithium transition metal oxide positive electrode material containing nickel, cobalt and manganese, and is also a lithium nickel-based oxide positive electrode material containing cobalt and manganese, and is also a lithium nickel cobalt-based oxide positive electrode material containing manganese. It can be understood that the lithium nickel cobalt manganese-based oxide positive electrode material includes lithium, non-lithium metal elements and oxygen elements; the non-lithium metal elements include nickel, cobalt and manganese. Non-limitingly, the mass proportion of lithium nickel cobalt manganese-based oxide positive electrode material in the positive electrode active material is 80% to 100%, which can be 90% to 100%, and further can be 95% to 100%, and can also be any of the following percentages or a range selected from any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.

[0309] In some embodiments, the lithium transition metal oxide positive electrode material includes a ternary positive electrode material, which may be a ternary positive electrode material. In the present application, the "ternary positive electrode material" is composed of Li element, nickel element, cobalt element, M2 element and oxygen element; wherein the M2 element may be a manganese element or an aluminum element. When the M2 element is manganese (Mn), the ternary positive electrode material is lithium nickel cobalt manganese oxide, which may be recorded as NCM, and when the M2 element is aluminum (Al), the ternary positive electrode material is lithium nickel cobalt aluminum oxide, which may be recorded as NCA.

[0310] In some embodiments, the positive electrode sheet includes a positive electrode active layer, the positive electrode active layer includes a positive electrode active material, and the positive electrode active material includes a lithium transition metal oxide positive electrode material; the thickness of the positive electrode active layer on one side of the negative electrode current collector is less than or equal to 50 μm, and the thickness of the positive electrode active layer on one side of the negative electrode current collector can also be any of the following thicknesses or a range selected from any two of the following thicknesses: 40 μm, 42 μm, 44 μm, 45 μm, 46 μm, 48 μm, 50 μm, etc. In this case, the positive electrode can provide a higher energy density, which can correspond to a thinner positive electrode active layer, and has better capacity matching with the negative electrode active layer, which is conducive to inhibiting negative electrode lithium deposition and extending the battery cycle life, including extending the normal temperature life.

[0311] In some embodiments, the positive electrode active material includes a lithium nickel-based oxide positive electrode material, and the lithium nickel-based oxide positive electrode material includes a lithium element, a non-lithium metal element, and an oxygen element; wherein the non-lithium metal element includes a nickel element.

[0312] In lithium nickel-based oxide cathode materials, the ratio of the atomic molar ratio of nickel element to the sum of the atomic molar ratios of non-lithium metal elements is denoted as R Ni When the lithium nickel-based oxide positive electrode material also contains cobalt, the ratio of the atomic molar ratio of the cobalt element to the sum of the atomic molar ratios of the non-lithium metal elements is recorded as RCo When the lithium nickel-based oxide positive electrode material also contains manganese, the ratio of the atomic molar ratio of the manganese element to the sum of the atomic molar ratios of the non-lithium metal elements is recorded as R Mn .

[0313] In some embodiments, R Ni It is 0.3~0.98, and can also be any of the following values, or a range consisting of any two of the following values: 0.3, 0.33, 1 / 3, 0.34, 0.35, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.92, 0.94, 0.95, 0.96, 0.97, 0.98, etc.

[0314] Without limitation, R Ni It can be greater than or equal to 0.6, and can also be any of the following values ​​or a range consisting of any two of the following values: 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.92, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1, etc.

[0315] Without limitation, R Ni It may be greater than or equal to 0.8, and may be any of the following values ​​or a range consisting of any two of the following values: 0.8, 0.85, 0.9, 0.92, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1, etc.

[0316] In some embodiments, R Co It is 0.02~0.25, and can also be any of the following values, or a range consisting of any two of the following values: 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.1, 0.12, 0.14, 0.15, 0.16, 0.18, 0.2, 0.22, 0.24, 0.25, etc.

[0317] In some embodiments, R Mn It is 0.1~0.35, and can also be any of the following values, or a range consisting of any two of the following values: 0.1, 0.12, 0.14, 0.15, 0.16, 0.18, 0.2, 0.22, 0.24, 0.25, 0.26, 0.28, 0.3, 0.32, 0.34, 0.35, etc.

[0318] In some embodiments, the lithium nickel cobalt-based oxide positive electrode material contains an M2 element, and the M2 element is a manganese element or an aluminum element; the sum of the atomic molar ratios of the nickel element, the cobalt element, and the M2 element relative to the sum of the atomic molar ratios of the non-lithium metal elements in the nickel cobalt-based oxide positive electrode material is denoted as R A , R A It is 0.42~1, and can be selected as 0.7~1.

[0319] The following is some description about the positive electrode.

[0320] The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active layer includes a positive electrode active material.

[0321] Without limitation, the weight percentage of the positive electrode active material in the positive electrode active layer may be greater than or equal to 80 wt %, and further may be greater than or equal to 90 wt %.

[0322] As a non-limiting example, the positive electrode current collector has two surfaces that are opposite to each other in its thickness direction, and the positive electrode active layer is disposed on any one or both of the two surfaces of the positive electrode current collector that are opposite to each other.

[0323] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. In the positive electrode current collector, the composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. In the positive electrode current collector, the composite current collector may be obtained by forming a metal material on a polymer material substrate. In the positive electrode current collector, non-limiting examples of the metal material may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. Non-limitingly, in the positive electrode current collector, the polymer material substrate may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0324] The type of positive electrode active material in the positive electrode sheet can refer to the description in the context of this application. Without limitation, other types of positive electrode active materials can also be introduced into the positive electrode active material. Other types of positive electrode active materials can include lithium-containing phosphate active materials.

[0325] In some embodiments, the positive electrode active material includes a lithium-containing phosphate-based positive electrode material.

[0326] In a non-limiting manner, the mass proportion of the lithium phosphate positive electrode material in the positive electrode active material is 0% to 5%, and can be optionally 0.1% to 5%.

[0327] It is understandable that the battery will be accompanied by lithium (Li) deintercalation and consumption during the charging and discharging process, and the content of Li in the positive electrode sheet is different when the battery is discharged to different states. In the exemplary description of the positive electrode active material in this application, unless otherwise specified, the content of Li can be the initial state of the material or the non-initial state after the charge and discharge cycle. The positive electrode active material is applied to the positive electrode in the battery system, and after the charge and discharge cycle, the content of Li in the positive electrode active material at the positive electrode usually changes. Among them, the content of Li can be measured by atomic molar content, but is not limited to this. Regarding "the content of Li is the initial state of the material", the initial state of the material refers to the state before being made into a positive electrode active layer. It can be understood that the new material or new substance obtained by appropriately modifying the listed positive electrode active materials is also within the scope of the positive electrode active material. The aforementioned appropriate modification refers to the acceptable modification method for the positive electrode active material, and non-limiting examples include one or more of coating modification and doping modification.

[0328] In the exemplary description of the positive electrode active material in this application, the content of oxygen (O) is only a theoretical state value. The release of oxygen from the lattice will cause the atomic molar content of oxygen to change, and the actual content of O will fluctuate. Among them, the content of O can be measured by atomic molar content, but is not limited to this.

[0329] In some embodiments, the positive electrode active layer may optionally include a binder. As a non-limiting example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin. Typically, the weight percentage of the binder in the positive electrode active layer may be 0 to 10 wt%, further 0 to 8 wt%, and further 1 wt% to 5 wt%, based on the total weight of the positive electrode active layer.

[0330] In some embodiments, the positive electrode active layer optionally includes a conductive agent. As a non-limiting example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. Typically, the weight percentage of the conductive agent in the positive electrode active layer may be 0 to 10 wt%, further 0 to 8 wt%, and further 0 to 5 wt%, based on the total weight of the positive electrode active layer.

[0331] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent to form a positive electrode slurry. Further, the positive electrode slurry is coated on at least one side of the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained. Cold pressing can be performed by a cold rolling mill. The type of solvent in the positive electrode slurry can include but is not limited to any of the aforementioned embodiments, for example, it can include N-methylpyrrolidone (NMP), and further can be NMP. The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector, or on both surfaces of the positive electrode collector. The solid content of the positive electrode slurry can be 40wt%~80wt%. The viscosity of the positive electrode slurry at room temperature can be adjusted to 5000mPa·s~25000mPa·s.

[0332] In some embodiments, the positive electrode active material includes a lithium transition metal oxide active material, and further, the mass proportion of the lithium transition metal oxide active material in the positive electrode active material can be greater than or equal to 50%, but is not limited thereto. When the positive electrode slurry is coated, the coating surface density (measured on the coating surface density on one side of the positive electrode current collector) on a dry weight basis (excluding the solvent) can be (0.05 ~ 0.6) g / 1540.25 mm 2 , optional: (0.1~ 0.3) g / 1540.25 mm 2 The compaction density of the positive electrode sheet can be 3.0 g / cm 3 ~ 4.2 g / cm 3 , optional 3.3 g / cm 3 ~ 3.8 g / cm 3 .

[0333] In some embodiments, the positive electrode active material includes a lithium-containing phosphate active material, and further, the mass proportion of the lithium-containing phosphate active material in the positive electrode active material can be greater than or equal to 50%, but is not limited thereto. When coating the positive electrode slurry, the coating surface density (measured as the coating surface density on one side) based on dry weight (excluding the solvent) can also be (0.1 ~0.5) g / 1540.25 mm 2 , optional: (0.2 ~ 0.4) g / 1540.25 mm 2 , but not limited to this. The compaction density of the positive electrode sheet can be 2.0g / cm 3 ~2.8 g / cm 3 , optional 2.3g / cm 3 ~2.6 g / cm 3 .

[0334] The "compacted density" used in this application has a well-known meaning in the art and is one of the reference indicators of material energy density. In this application, unless otherwise specified, the compacted density of the positive electrode sheet refers to the ratio of the mass of the positive electrode active layer to its volume, and the compacted density of the negative electrode sheet refers to the ratio of the mass of the negative electrode active layer to its volume.

[0335] The following are some additional descriptions about the negative electrode.

[0336] The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active layer includes a negative electrode active material.

[0337] Without limitation, the weight percentage of the negative electrode active material in the negative electrode active layer may be greater than or equal to 80 wt %, and further may be greater than or equal to 90 wt %.

[0338] As a non-limiting example, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active layer is disposed on any one or both of the two surfaces facing each other of the negative electrode current collector.

[0339] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. In the negative electrode current collector, the composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. In the negative electrode current collector, the composite current collector may be formed by forming a metal material on a polymer material substrate. In the negative electrode current collector, non-limiting examples of the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In a non-limiting manner, in the negative electrode current collector, the polymer material substrate may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0340] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As a non-limiting example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. Silicon-based materials may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials or substances, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0341] In some embodiments, the negative electrode active layer may optionally include a binder. Without limitation, the binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS). Without limitation, the weight percentage of the binder in the negative electrode active layer may be 0wt% to 20wt%, further 0wt% to 10wt%, further 0 to 5wt%, further 1wt% to 5wt%, and further 1wt% to 3wt%.

[0342] The type of negative electrode active material can also be referred to the context of this application.

[0343] In some embodiments, the negative electrode active layer may optionally include a conductive agent. In a non-limiting manner, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In a non-limiting manner, the weight percentage of the conductive agent in the negative electrode active layer may be 0wt% to 15wt%, further optionally 0wt% to 10wt%, and further optionally 0wt% to 5wt%.

[0344] In some embodiments, the negative electrode active layer may optionally include other additives, such as a thickener (e.g., sodium carboxymethyl cellulose (CMC-Na)). In a non-limiting manner, the weight percentage of other additives in the negative electrode active layer may be 0 wt% to 15 wt%, further 0 wt% to 10 wt%, further 0 wt% to 5 wt%, further 0 wt% to 3 wt%, and further 0 wt% to 2 wt%.

[0345] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry. Further, the negative electrode slurry is coated on at least one side of the surface of the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. Cold pressing can be performed using a cold rolling mill. The surface of the negative electrode collector coated with the negative electrode slurry can be on a single surface of the negative electrode collector or on both surfaces of the negative electrode collector. The solid content of the negative electrode slurry can be 30 wt%~70wt%, and can be optionally 40wt%~60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000 mPa·s~10000 mPa·s, and can be optionally 3000 mPa·s~10000 mPa·s. When coating the negative electrode slurry, the coating surface density on one side of the negative electrode current collector can be 7.5 mg / cm based on dry weight (excluding solvent). 2 ~22 mg / cm 2 , optional: (0.12~0.2)g / 1540.25mm 2 The compaction density of the negative electrode sheet can be 1.0 g / cm 3 ~ 2.0g / cm 3 , optional 1.0 g / cm 3 ~ 1.8 g / cm 3 .

[0346] The electrolyte is exemplarily described below.

[0347] The electrolyte has the function of conducting ions between the positive electrode and the negative electrode. The electrolyte includes electrolyte salt and solvent.

[0348] In some embodiments, the electrolyte is a non-aqueous electrolyte. The non-aqueous electrolyte may include an electrolyte salt and a non-aqueous solvent.

[0349] In some embodiments, the molar volume concentration of the electrolyte salt in the electrolyte can generally be 0.5 mol / L~5 mol / L, can be 0.5 mol / L~2 mol / L, can be further selected as 0.6 mol / L~1.8 mol / L, can be further selected as 0.7 mol / L~1.2 mol / L, can also be any of the following concentrations or a range consisting of any two of the following concentrations: 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.8 mol / L, 2 mol / L, etc.

[0350] In some embodiments, the electrolyte salt includes an electrolyte lithium salt, and may further be an electrolyte lithium salt. Without limitation, other types of electrolyte salts may also be introduced into the electrolyte.

[0351] In some embodiments, the electrolyte salt includes an electrolyte lithium salt. Without limitation, the electrolyte lithium salt may include lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ) and lithium hexafluoroarsenate (LiAsF 6 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO 2 F 2 ), one or more of lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorooxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0352] The type of non-aqueous solvent in the electrolyte can refer to the description in the context of this application. Without limitation, other types of non-aqueous solvents can also be introduced into the electrolyte. In some embodiments, the non-aqueous solvent can include ethylene carbonate (EC, ), propylene carbonate (PC, )、ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC, ), one or more of propyl acetate, methyl propionate, ethyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0353] The electrolyte includes additives, including at least the first additive mentioned above.

[0354] The types of additives in the electrolyte can refer to the description in the context of this application. Without limitation, other types of additives can also be introduced into the electrolyte. Other types of additives can include negative electrode film-forming additives, positive electrode film-forming additives, and can also include additives that can improve certain properties of the battery, such as additives that improve the overcharge performance of the battery, additives that improve the high temperature or low temperature performance of the battery, etc.

[0355] The separator is exemplarily described below.

[0356] In some embodiments, the lithium-ion secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0357] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.

[0358] In some embodiments, the thickness of the isolation film is 6 μm to 40 μm, and optionally 6 μm to 20 μm.

[0359] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0360] In some embodiments, the lithium-ion secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0361] In some embodiments, the outer packaging of the lithium ion secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the lithium ion secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and further, non-limiting examples of plastic can include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0362] A lithium-ion secondary battery includes at least one battery cell. A lithium-ion secondary battery may include one or more battery cells.

[0363] The present application has no particular restrictions on the shape of the battery cell, which can be cylindrical, square or any other shape. For example, Figure 1 The battery cell 5 is a square structure as an example.

[0364] In some embodiments, reference Figure 2, the outer packaging may include a battery case 51 and a cover plate 53. Among them, the battery case 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The battery case 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to actual needs. In some embodiments, the injection coefficient of the electrolyte is greater than or equal to 1.6g / Ah.

[0365] The lithium-ion secondary battery may be a battery device 4 or a battery pack 1 .

[0366] The battery device includes at least one battery cell. The number of battery cells contained in the battery device can be one or more, and those skilled in the art can select a suitable number according to the application and capacity of the battery device.

[0367] Figure 3 4 is an example of a battery device. Figure 3 In the battery device 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery device 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0368] Optionally, the battery device 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0369] In some embodiments, the battery devices described above may also be assembled into a battery pack. The number of battery devices contained in the battery pack may be one or more. Those skilled in the art may select a suitable number according to the application and capacity of the battery pack.

[0370] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery devices 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery devices 4. The plurality of battery devices 4 can be arranged in the battery box in any manner.

[0371] In a second aspect of the present application, a method for preparing a lithium ion secondary battery is provided, which can be used to prepare the lithium ion secondary battery of the first aspect of the present application.

[0372] In some embodiments, a method for preparing a lithium ion secondary battery is provided, comprising the following steps:

[0373] S100: placing an electrode assembly including a positive electrode sheet, a separator and a negative electrode sheet in a battery housing; wherein a separator is provided between the positive electrode sheet and the negative electrode sheet; wherein the positive electrode sheet includes a positive electrode active layer, the positive electrode active layer includes a positive electrode active material, the positive electrode active material includes a lithium transition metal oxide positive electrode material, and the D v 3 greater than or equal to 1 μm;

[0374] S200: injecting electrolyte into the battery housing, and allowing the electrolyte to soak the positive electrode sheet and the negative electrode sheet to form the electrolyte; wherein the electrolyte includes an electrolyte salt, a non-aqueous solvent and an additive; the additive includes a first additive, and the first additive is an acetylene base additive containing a Lewis base nitrogen heterocycle.

[0375] The definitions of positive electrode active materials and additives can be found in the context of this application.

[0376] The prepared lithium ion secondary battery has the advantages of the lithium ion secondary battery described in the first aspect of the present application.

[0377] In some embodiments, in step 200, after injecting electrolyte into the battery casing, a lithium-ion secondary battery assembly is obtained.

[0378] In some embodiments, the lithium-ion secondary battery assembly may correspond to a state before a formation treatment is performed.

[0379] Without limitation, the formation temperature may be 45° C., but is not limited thereto.

[0380] In some embodiments, the formation can be performed at 45° C. using a method comprising the following steps (steps S1, S2, S3 and S4 are performed in sequence):

[0381] S1) Charge at 0.05C for 14 minutes to 3V, and let stand for 10 minutes;

[0382] S2) Charge at 0.1C to 3.4V and let stand for 10 minutes;

[0383] S3) Charge at 0.2C to 3.65V and let stand for 10 minutes;

[0384] S4) Charge at 0.2C to 3.75V and let stand for 10 minutes;

[0385] End of transformation.

[0386] In the present application, the concentrations of additives and electrolyte salts involved in “injecting electrolyte into the battery casing” correspond to “initial concentrations”, which may correspond to the initial mass proportion of the additives in the electrolyte and the initial molar volume concentration of the electrolyte salt in the electrolyte, respectively.

[0387] In some embodiments, in the step of injecting electrolyte into the battery housing, the initial mass percentage of the first additive in the electrolyte is 0.1%~5%, which can be optionally 0.1%~3%, or any of the following percentages or a range consisting of any two of the following percentages: 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.6%, 0.75%, 0.8%, 0.9%, 1%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.

[0388] The first additive involved in the present application can be purchased from the market, or synthesized using existing methods in the field of organic chemical synthesis. When the structural formula of the first additive is selected, those skilled in the art can select a suitable organic synthesis method to prepare the target compound; further, those skilled in the art can also identify the structure of the prepared first additive by one or more of the following detection methods, including but not limited to: nuclear magnetic resonance hydrogen spectrum ( 1 H NMR) method, high performance liquid chromatography (HPLC) method, matrix-assisted laser desorption-to-time of flight mass spectrometry (MADI-TOF) method, Fourier transform infrared (FT-IR) spectroscopy, etc.

[0389] Those skilled in the art know that after the formation treatment, the content of some additive components in the electrolyte may change. As a non-limiting example, for example, some film-forming additive components are reduced in content due to their participation in the formation of the solid electrolyte interface film of the positive electrode and / or the negative electrode. As a non-limiting example, the content of the first additive in the electrolyte is generally reduced after the formation treatment relative to the electrolyte before the formation treatment.

[0390] In some embodiments, after the formation treatment, in the prepared lithium ion secondary battery, the content of each additive can refer to the first aspect of the present application.

[0391] In the lithium-ion secondary battery assembly, the types of electrolyte salt and non-aqueous solvent in the electrolyte can refer to the first aspect of the present application. After the chemical formation treatment, the mass proportions of the electrolyte salt and the solvent in the electrolyte may change.

[0392] In the lithium-ion secondary battery assembly, the material composition and size of the positive electrode sheet, the negative electrode sheet and the separator can refer to the first aspect of the present application. The size of the positive electrode sheet, the negative electrode sheet and the separator in the lithium-ion secondary battery assembly may be slightly different from the size in the lithium-ion secondary battery of the first aspect.

[0393] In some embodiments, the lithium ion secondary battery described in the first aspect of the present application is prepared.

[0394] In some embodiments of the third aspect of the present application, an electrical device is provided, comprising at least one of the lithium ion secondary battery described in the first aspect of the present application and the lithium ion secondary battery prepared by the preparation method of the lithium ion secondary battery described in the second aspect of the present application.

[0395] An electric device including the lithium ion secondary battery can have the advantageous effects of the lithium ion secondary battery.

[0396] In some embodiments, an electric device includes a lithium-ion secondary battery according to any embodiment of the present application.

[0397] Lithium-ion secondary batteries can be used as power sources for electrical devices, or as energy storage units for electrical devices. Electrical devices may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. Among them, mobile devices may be, for example, mobile phones, laptop computers, etc.; electric vehicles may be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, electric motorcycles, electric tools, etc., but are not limited thereto. The electrical device may also be used in fields such as aerospace, and may also be used in energy storage power supply systems such as hydropower, thermal power, wind power and solar power stations.

[0398] As an electrical device, a lithium-ion secondary battery can be selected according to its usage requirements.

[0399] Figure 6 The power consumption device 6 is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of lithium-ion secondary batteries, a battery device or a battery pack can be used.

[0400] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a lithium-ion secondary battery may be used as a power source.

[0401] In a fourth aspect of the present application, a lithium-ion secondary battery assembly is provided, which is the lithium-ion secondary battery assembly in the method for preparing the lithium-ion secondary battery described in the second aspect of the present application.

[0402] Below, some embodiments of the present application are described. The described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The embodiments described below are exemplary and are only used to explain the present application, and should not be understood as limitations on the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0403] If the techniques or conditions are not specified in the examples, the above description, or the techniques or conditions described in the literature in the field, or the product instructions are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially, or can be synthesized in a conventional manner from commercially available products.

[0404] In the following examples, room temperature refers to 20°C to 30°C.

[0405] In the following examples, unless otherwise specified, the parameters involved can be confirmed by referring to the test methods described above. v 50 and D v 3. D of negative electrode active material v 50 Malvern 2000 (MasterSizer2000) laser particle size analyzer can be used for testing; For the specific surface area of ​​the negative electrode active material, the nitrogen adsorption specific surface area analysis test method can be used for testing, and the nitrogen adsorption specific surface area analysis test is performed by the Tri StarII specific surface and pore analyzer of Micromeritics, USA, and the specific surface area is calculated by the BET (Brunauer EmmettTeller) method. For the carbon coating layer, the transmission electron microscope JEM-F200 combined with EDS (Energy Dispersive Spectrometer) can be used for testing. For example, for the ion conductivity test of the electrolyte, the DDSJ-318 conductivity meter is used, and the HG-T 4067-2015 detection method is referred to. For the various organic components in the prepared lithium-ion secondary battery, the test can be carried out with reference to the relevant standards such as "GB / T 9722-2023 General Rules for Gas Chromatography of Chemical Reagents".

[0406] Among them, compound IIa ( , 2-propyn-1-yl 1H-imidazole-1-carboxylate) as an example, the structure identification and quantitative analysis can be carried out by the following method:

[0407] In the nuclear magnetic resonance hydrogen spectrum, the H in the methylene group connected to the triple bond may have a characteristic peak near 4.677 ppm; the hydrogen between the two nitrogen atoms in the imidazole ring may have a characteristic peak near 8.095 ppm; the integrated area of ​​each characteristic peak is calculated, and then compared with the integrated area of ​​the peak of the internal standard trifluoromethylbenzene, the content of compound IIa can be quantitatively calculated.

[0408] Nuclear magnetic resonance spectroscopy (NMR) can be used to detect the mass fraction of additives in the electrolyte. The test steps can be: add 500 μL of deuterated reagent to the NMR tube in a glove box filled with nitrogen, take 100 μL of non-aqueous electrolyte sample and add it to the NMR tube, shake the NMR tube to dissolve the non-aqueous electrolyte into the deuterated reagent, and use the Oxford Instruments desktop NMR spectrometer X-Pulse for testing. Since non-aqueous electrolytes are very sensitive to moisture, hydrogen spectrum NMR testing and sample preparation are all carried out in a nitrogen atmosphere (H 2 O content is less than 0.1 ppm, O 2 The content is less than 0.1 ppm). At the same time, the instruments related to the test also need to be pre-washed with pure water and dried in a vacuum environment at 60°C for more than 48 hours. Among them, the deuterated reagent is prepared according to the following steps: deuterated dimethyl sulfoxide (DMSO-d6), deuterated acetonitrile and trifluoromethylbenzene are dried with 4A molecular sieves at a temperature above 25°C for more than 3 days, so that the water content of all reagents is less than 3ppm. The moisture test instrument can be the 831 KF coulometric moisture tester of Swiss Metrohm Co., Ltd. After that, 10mL of dried DMSO-d6 and 300 μL of dried internal standard trifluoromethylbenzene are mixed evenly in a glove box filled with nitrogen to obtain the first solution, 10mL of dried deuterated acetonitrile and 300 μL of dried internal standard trifluoromethylbenzene are mixed evenly to obtain the second solution, and the first solution and the second solution are mixed evenly to obtain the deuterated reagent.

[0409] In the following embodiments, the electrolyte salt is an electrolyte lithium salt, and the compound IIa is a non-limiting example as the first additive.

[0410] 1. Preparation of lithium-ion secondary batteries

[0411] Example 1.

[0412] (1) Positive electrode

[0413] The positive electrode active material (Ni55), conductive agent carbon black (Super P) and binder polyvinylidene fluoride (PVDF) were mixed in a solvent N-methylpyrrolidone (NMP) at a weight ratio of 96:3:1 to obtain a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry was coated on both sides of the positive electrode current collector aluminum foil, and the coating surface density on one side of the positive electrode current collector was 0.27g / 1540.25mm 2 Through drying, cold pressing, slitting, cutting and other processes, the positive electrode sheet is obtained, and the compaction density is about 3.4 g / cm 3 .

[0414] In this example, the positive electrode active material is a ternary positive electrode material with a chemical formula of LiNi 0.55 C O0.12 Mn 0.33 O 2 , D of the positive electrode active material v 50 is 4 μm, D v 3 is 1.2 μm, and the average particle size of primary particles in the positive electrode active material (D 1 ) is 2 μm, and the D v 50 relative to the average particle size of primary particles in the positive electrode active material (D 1 ) is about 2.

[0415] (2) Negative electrode

[0416] The negative electrode active material (coated graphite), conductive agent carbon black (Super P), styrene-butadiene rubber (SBR) and thickener sodium carboxymethyl cellulose (CMC-Na) were mixed uniformly in a solvent deionized water at a weight ratio of 97:0.5:1.5:1 to prepare a negative electrode slurry with a solid content of 50wt%. The negative electrode slurry was coated on both sides of the negative electrode current collector copper foil, and the coating surface density on one side of the negative electrode current collector was 0.16g / 1540.25mm 2 Through drying, cold pressing, slitting and cutting processes, the negative electrode sheet is obtained. The compaction density of the negative electrode sheet is 1.65 g / cm 3 .

[0417] In this example, the negative electrode active material is coated graphite, including a graphite body and an amorphous carbon coating layer located on the surface of the graphite body. The graphite body is artificial graphite, and the amorphous carbon coating layer accounts for about 1.43% of the mass of the coated graphite. v 50 is 11μm, and the specific surface area is 1.5m 2 / g.

[0418] (3) Isolation film: conventional PE film is used as isolation film

[0419] (4) Preparation of electrolyte: Add additives to the non-aqueous solvent, mix well, then add fully dried electrolyte lithium salt, mix well to fully dissolve the electrolyte lithium salt, and prepare the electrolyte.

[0420] The electrolyte salt in the electrolyte is an electrolyte lithium salt, and further, the electrolyte lithium salt is lithium hexafluorophosphate, and the initial concentration of lithium hexafluorophosphate in the electrolyte is 1 mol / L. The non-aqueous solvent is EC (ethylene carbonate), DMC (dimethyl carbonate) and EMC (ethyl methyl carbonate) in a mass ratio of 2:3:5. The additives are 2-propynyl-1-1H-imidazole-1-carboxylate (the first additive) and FEC (fluoroethylene carbonate). The structure of the first additive is shown in formula (IIa), also recorded as compound IIa, and the initial mass proportion of compound IIa in the electrolyte is 2%, and the initial mass proportion of FEC in the electrolyte is 1%.

[0421]

[0422] (5) Preparation of lithium-ion secondary batteries: stack and wind the positive electrode sheet, separator and negative electrode sheet in order to obtain a bare cell (electrode assembly); weld the tabs to the bare cell, place the bare cell into an aluminum shell, and bake it at 80°C to remove water. Then inject electrolyte and seal it. Then, go through the steps of standing, hot and cold pressing, formation, shaping, capacity testing, etc. to obtain a lithium-ion secondary battery.

[0423] After injecting the electrolyte, a lithium-ion secondary battery assembly is obtained.

[0424] In this example, the static infiltration parameters are: 18 hours at room temperature and then 6 hours at 45°C.

[0425] In this example, the formation parameters are as follows: at 45°C,

[0426] 0.05C charge for 14 minutes to 3.0V, let stand for 10 minutes;

[0427] 0.1C charge to 3.4V and let stand for 10 minutes;

[0428] 0.2C charge to 3.65V, let stand for 10min;

[0429] 0.2C charge to 3.75V, let stand for 10min;

[0430] The transformation is finished.

[0431] In this example, the prepared lithium-ion secondary battery was disassembled, and the content of components in the electrolyte was detected. The first additive (compound II) was 1.2% by mass percentage in the electrolyte.

[0432] Example 2-3. A lithium-ion secondary battery was prepared by the same method as in Example 1, except that: in the step of preparing the positive electrode sheet, the positive electrode active material used was different, and the main change was D v 3. The relevant parameters of the positive electrode active material can be found in Table 1. The remaining operation steps are the same as those in Example 1.

[0433] In Example 2, the positive electrode active material D v 3 is about 1 μm;

[0434] In Example 3, the positive electrode active material D v 3 is about 1.5μm.

[0435] Example 4-5. A lithium-ion secondary battery was prepared by the same method as in Example 1, except that: in the step of preparing the positive electrode sheet, the positive electrode active material used was different, and the main change was D v 50, the relevant parameters of the positive electrode active material can be found in Table 1. The remaining operation steps are the same as those in Example 1.

[0436] In Example 4, the positive electrode active material D v 50 is 2.7 μm;

[0437] In Example 5, the positive electrode active material D v 50 is 4.8μm.

[0438] Example 6 A lithium ion secondary battery was prepared by using a method substantially the same as that of Example 1, except that in the step of preparing the positive electrode sheet, different positive electrode active materials were used. The relevant parameters of the positive electrode active materials can be found in Table 1. The remaining steps were the same as those of Example 1.

[0439] In Example 6, the positive electrode active material is a ternary positive electrode material, and the chemical formula is LiNi 0.55 C O0.10 Mn 0.35 O 2 .

[0440] Example 7-8. A lithium-ion secondary battery is prepared by the same method as in Example 1, except that in the step of preparing the negative electrode sheet, the negative electrode active material D v 50 and specific surface area are different. Please refer to Table 1. The remaining steps are the same as those in Example 1.

[0441] In Example 7, the negative electrode active material D v 50 is 8.1μm, and the specific surface area is 2.8m 2 / g.

[0442] In Example 8, the negative electrode active material D v50 is 19.8μm, and the specific surface area is 0.5m 2 / g.

[0443] Example 9-10. A lithium-ion secondary battery was prepared by a method substantially the same as that of Example 1, except that the prepared electrolyte composition was different, the initial concentration of the first additive (Compound IIa) in the electrolyte was different, and the initial concentration of FEC remained unchanged. The remaining steps were the same as those of Example 1. See Table 2.

[0444] In Example 9, the initial mass proportion of the first additive (Compound IIa) in the electrolyte is 0.1%.

[0445] In Example 10, the initial mass proportion of the first additive (Compound IIa) in the electrolyte is 5%.

[0446] Examples 11-17. A lithium ion secondary battery was prepared by a method substantially the same as that of Example 1, except that the composition of the prepared electrolyte was different and the composition of the additive in the electrolyte was different. The remaining steps were the same as those of Example 1. Please refer to Table 2.

[0447] In Examples 11 and 12, a second additive was added.

[0448] In Example 11, the additive composition in the electrolyte is 2% of Compound IIa and 0.3% of TDI (toluene diisocyanate) based on the initial mass percentage in the electrolyte.

[0449] In Example 12, the additive composition in the electrolyte is: 2% of Compound IIa and 0.3% of TMSP (tris(trimethylsilyl)phosphate), based on the initial mass percentage in the electrolyte.

[0450] In Example 13, the additive composition in the electrolyte is 2% of Compound IIa and 0.5% of lithium difluorophosphate, based on the initial mass percentage in the electrolyte.

[0451] In Example 14, the additive composition in the electrolyte is: 1% of Compound IIa and 0.5% of LiDFOB (lithium difluorooxalatoborate), based on the initial mass percentage in the electrolyte.

[0452] In Example 15, the additive composition in the electrolyte is: 1% of Compound IIa and 0.3% of TMSB (tris(trimethylsilyl)borate), based on the initial mass percentage in the electrolyte.

[0453] In Example 16, the additive composition in the electrolyte is 2% of Compound IIa and 1% of DTD (vinyl sulfate) based on the initial mass percentage in the electrolyte.

[0454] In Example 17, the additive composition in the electrolyte is: 1% of Compound IIa and 2% of FEC (fluoroethylene carbonate), based on the initial mass percentage in the electrolyte.

[0455] Example 18 A lithium ion secondary battery was prepared by a method substantially the same as that of Example 1, except that the prepared electrolyte composition, the electrolyte additive composition and the electrolyte lithium salt composition were different, and the remaining steps were the same as those of Example 1. See Table 2.

[0456] In Example 18, the additive composition in the electrolyte is: 1% of the first additive (Compound IIa), 0.3% of TMSP and 2% of FEC, based on the initial mass percentage in the electrolyte; based on the initial molar volume concentration in the electrolyte, the electrolyte lithium salt is 0.3 mol / L LiFSI (lithium bis(fluorosulfonyl)imide) and 0.7 mol / L LiPF6 (lithium hexafluorophosphate).

[0457] Example 19 A lithium ion secondary battery was prepared by using a method substantially the same as that of Example 4, except that in the step of preparing the negative electrode sheet, the negative electrode active material was different, and the remaining steps were the same as those of Example 4. See Table 1.

[0458] In Example 19, the negative electrode active material is a carbon-based material and a silicon-based material in a mass ratio of 97:3, that is, the mass ratio of the silicon-based material in the negative electrode active material is 3%. The carbon-based material is the same as in Example 1; the silicon-based material is a silicon-carbon composite material, including a porous carbon matrix and elemental silicon deposited in the pores of the porous carbon matrix, and the mass ratio of silicon element to carbon element is 1:1. v 1 and D v 50 is close to Example 1.

[0459] Comparative Example 1. A lithium ion secondary battery was prepared by using a method substantially the same as that of Example 1, except that the prepared electrolyte composition was different, the first additive was omitted from the electrolyte, and the initial concentration of the electrolyte lithium salt remained unchanged. The remaining steps were the same as those of Example 1.

[0460] Comparative Example 2 A lithium-ion secondary battery was prepared by using a method substantially the same as that of Example 17, except that the electrolyte composition was different, the first additive was omitted from the electrolyte, and the initial concentrations of the other additives and the electrolyte lithium salt remained unchanged. The remaining steps were the same as those of Example 17.

[0461] Comparative Example 3 A lithium ion secondary battery was prepared by using a method substantially the same as that of Example 18, except that the electrolyte composition was different, the first additive was omitted from the electrolyte, and the initial concentrations of the other additives and the electrolyte lithium salt remained unchanged. The remaining steps were the same as those of Example 18.

[0462] Comparative Example 4 A lithium ion secondary battery was prepared by a method substantially the same as that of Example 19, except that the prepared electrolyte composition was different, the first additive was omitted from the electrolyte, and the initial concentration of the electrolyte lithium salt remained unchanged. The remaining steps were the same as those of Example 19.

[0463] Comparative Example 5. A lithium-ion secondary battery was prepared by substantially the same method as in Example 1, except that: the electrolyte composition was different, and the first additive in the electrolyte was replaced by methyl carboxylic acid-2-propynyl ester ( ), the initial concentration of the electrolyte lithium salt remains unchanged. The remaining steps are the same as those in Example 1.

[0464] Comparative Example 6. A lithium-ion secondary battery was prepared by the same method as in Example 19, except that different positive electrode active materials were used in the process of preparing the positive electrode sheet. v 3. The relevant parameters of the positive electrode active material can be found in Table 1. The remaining operation steps are the same as those in Example 1.

[0465] In Comparative Example 6, the positive electrode active material D v 3 is about 0.5μm.

[0466] Comparative Example 7. A lithium-ion secondary battery was prepared by using a method substantially the same as that of Example 7, except that in the process of preparing the positive electrode sheet, a different positive electrode active material was used, and the positive electrode active material of Comparative Example 6 was used. The relevant parameters of the positive electrode active material can be found in Table 1. The remaining steps were the same as those of Example 7.

[0467] 2. Test and analysis methods

[0468] 1. Conductivity of electrolyte

[0469] Use DDSJ-318 conductivity meter. Refer to page 5 of the industry standard HG / T4067-2015 "Lithium Hexafluorophosphate Electrolyte".

[0470] Test steps (density meter method):

[0471] Use a dry, clean, corrosion-resistant sample bottle to take about 100 mL of sample, seal it in a constant temperature water bath at 25℃±0.5℃, shake it from time to time, and when the sample temperature is constant, replace the sample bottle cap with a rubber stopper with an electrode. When the temperature is within the range of 25℃±0.5℃, read the data in the conductivity meter, which is the conductivity of the sample being tested.

[0472] 2. Initial DC internal resistance (DCR) test:

[0473] At 25°C, the battery to be tested is charged to 3.65V at 0.5C constant current, and then charged to 0.05C at constant voltage; the battery is discharged at 0.5C constant current for 30 minutes to adjust the battery to 50% SOC, at which time the battery voltage is recorded as U1; the battery is discharged at 4C constant current for 30 seconds, with 0.1 second sampling, and the voltage at the end of discharge is recorded as U2. The discharge DCR of the battery at 50% SOC represents the initial DCR of the battery, and the initial DCR of the battery = (U1-U2) / I, where I is the current value corresponding to 4C.

[0474] The test results can be found in “Battery DCR0” in Table 3.

[0475] 3. Normal temperature cycle performance (25°C)

[0476] At 25°C, charge the battery to be tested at 1C constant current to 3.65V, then charge at 3.65V constant voltage to a cut-off current of 0.05C, leave for 10 minutes, then discharge at 1C constant current to 2.5V, leave for 5 minutes. This is a charge and discharge cycle. Record the discharge capacity at this time as C 0 Repeat this charge and discharge cycle process for the same battery, and record the discharge capacity C of the first, second, and nth cycles. n , where the number of cycles is at least 300.

[0477] Record the battery's cycle capacity retention rate P300 = C when the cycle is 300 cycles 300 / C 0 ×100%.

[0478] The test results can be found in the "Capacity retention rate after 300 cycles at room temperature" in Table 3. The higher the test value, the better the room temperature cycle life.

[0479] 4. High temperature cycle performance (45°C)

[0480] At 45°C, charge the battery to be tested at 1C constant current to 3.65V, then charge at 3.65V constant voltage to a cut-off current of 0.05C, leave for 10 minutes, then discharge at 1C constant current to 2.5V, leave for 5 minutes. This is a charge and discharge cycle. Record the discharge capacity at this time as C 0 Repeat this charge and discharge cycle process for the same battery, and record the discharge capacity C of the first, second, and nth cycles. n , where the number of cycles is at least 600.

[0481] Record the battery's cycle capacity retention rate when the cycle is 600 times P600 = C 600 / C 0 ×100%.

[0482] The test results can be found in the "45°C cycle 600 cycle capacity retention rate" in Table 3. The higher the test value, the better the high temperature cycle life.

[0483] 3. Test Analysis Results

[0484] The 25°C ionic conductivity of the electrolytes in Examples 1-19 is in the range of 8 mS / cm to 20 mS / cm.

[0485] Table 1.

[0486]

[0487] In Table 1, B1 represents the D of the positive electrode active material. v 50 and the average particle size of primary particles in the positive electrode active material (D 1 ) ratio.

[0488] Table 2.

[0489]

[0490] In the lithium-ion secondary batteries prepared by chemical formation, the battery cells were disassembled to test the electrolyte components: the mass percentages of the first additive in the electrolytes of Examples 1-19 were all in the range of 0.02% to 3.6%. After chemical formation, the mass percentage of the first additive in the electrolyte in Example 1 was about 1.2% (initial concentration before formation was 2%), the mass percentage of the first additive in the electrolyte in Example 9 was about 0.02% (initial concentration before formation was 0.1%), and the mass percentage of the first additive in the electrolyte in Example 10 was about 3.6% (initial concentration before formation was 5%); the mass percentages of other additives in the electrolytes of Examples 11-18 were reduced to varying degrees and all still had residues.

[0491] In the lithium-ion secondary battery prepared by chemical formation, the battery cells were disassembled to test the electrolyte components: in Example 15, the mass ratio of the second additive to the first additive was in the range of 0.1~50, and the mass percentage of the second additive in the electrolyte was in the range of 0.1%~1%, and further in the range of 0.1%~0.3%; in Example 11, the mass ratio of the third additive to the first additive was in the range of 0.1~50, and the mass percentage of the second additive in the electrolyte was in the range of 0.1%~1%, and further in the range of 0.1%~0.3%; in Examples 12-14, the mass ratio of the fourth additive to the first additive was in the range of 0.01~100, and the mass percentage of the fourth additive in the electrolyte was in the range of 0.1%~2%, and further in the range of 0.1%~0.5%.

[0492] Table 3.

[0493]

[0494] The lithium-ion secondary batteries prepared in Examples 1-19 all have significantly improved high-temperature performance and also have good room-temperature performance.

[0495] In Comparative Examples 1-4, the first additive is omitted relative to Examples 1 and 17-19, respectively. Both the high temperature performance and the room temperature performance of Comparative Examples 1-4 are significantly deteriorated.

[0496] In Comparative Example 5, the first additive in Example 1 is replaced with an acetylene additive that does not contain a Lewis base nitrogen heterocycle. Both the high-temperature performance and the room-temperature performance of Comparative Example 5 are significantly deteriorated.

[0497] Comparative Example 6: Reduce the D of the positive electrode active material in Example 19 v 3. The high temperature performance and room temperature performance of Comparative Example 6 are both deteriorated. Compared with Example 7, the high temperature performance and room temperature performance of Comparative Example 7 are also deteriorated.

[0498] The description of each embodiment and example above tends to emphasize the differences between each embodiment and example, and the same or similar parts can be referenced to each other. For the sake of brevity, this article will not repeat them. The technical features of the above-described embodiments and examples can be combined arbitrarily. For the sake of brevity, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0499] It should be noted that the present application is not limited to the above-mentioned embodiments and examples. The above-mentioned embodiments and examples are only examples. Within the scope of the technical solution of the present application, the embodiments and examples that have the same structure as the technical idea and play the same effect are all included in the technical scope of the present application. The above-described embodiments and examples only express several embodiments and examples of the present application, and the description is relatively detailed, but it cannot be understood as a limitation on the scope of the patent. In addition, without departing from the scope of the subject matter of the present application, various modifications that can be thought of by a person skilled in the art to the embodiments or examples, and other methods of combining some of the constituent elements in the embodiments or examples are also included in the scope of the present application.

Claims

1. A lithium ion secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein a separator is arranged between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet comprises a positive electrode active layer, and the positive electrode active layer comprises a positive electrode active material; the electrolyte comprises an electrolyte salt, a non-aqueous solvent and an additive; The positive electrode active material comprises a lithium transition metal oxide positive electrode material. v 3 greater than or equal to 1 μm; The additives include a first additive, which is an acetylene base additive containing a Lewis base nitrogen heterocycle.

2. The lithium ion secondary battery according to claim 1, characterized in that: The positive electrode active material D v 3 is 1μm~2μm.

3. The lithium ion secondary battery according to claim 2, characterized in that: The positive electrode active material D v 3 is 1μm~1.6μm.

4. The lithium-ion secondary battery according to claim 1, characterized in that: The average particle size of primary particles in the positive electrode active material is 1.1 μm to 3.0 μm.

5. The lithium ion secondary battery according to claim 4, characterized in that: The average particle size of primary particles in the positive electrode active material is 1.2 μm to 2.5 μm.

6. The lithium ion secondary battery according to claim 1, characterized in that: The positive electrode active material D v The ratio of 50 to the average particle size of the primary particles in the positive electrode active material is recorded as B1; The positive electrode sheet meets one or more of the following characteristics: (a1) D of the positive electrode active material v 50 is 2.5μm~ 5μm; (a2) B1 is 1~2.

5.

7. The lithium ion secondary battery according to claim 6, characterized in that: The positive electrode sheet meets one or more of the following characteristics: (a1') D of the positive electrode active material v 50 is 3μm~4.5μm; (a2')B1 is 1.8~2.

3.

8. The lithium ion secondary battery according to any one of claims 1 to 7, characterized in that The negative electrode sheet comprises a negative electrode active layer, and the negative electrode active layer comprises a negative electrode active material; v 50 is 8μm~20μm.

9. The lithium ion secondary battery according to claim 8, characterized in that: The negative electrode active material D v 50 is 10μm~18μm.

10. The lithium ion secondary battery according to any one of claims 1 to 7, characterized in that The negative electrode plate comprises a negative electrode active layer, and the negative electrode active layer comprises a negative electrode active material; the negative electrode active material comprises at least one of a carbon-based material and a silicon-based material; The negative electrode plate meets one or more of the following characteristics: (b1) the mass proportion of the silicon-based material in the negative electrode active material is 0-30%; (b2) The silicon-based material includes a silicon-carbon composite material, which includes a porous carbon matrix and elemental silicon located in the pores of the porous carbon matrix; the mass proportion of the silicon-carbon composite material in the silicon-based material is 80% to 100%.

11. The lithium ion secondary battery according to any one of claims 1 to 7, characterized in that: The mass percentage of the first additive in the electrolyte is less than 3.6%.

12. The lithium ion secondary battery according to claim 11, characterized in that: The mass percentage of the first additive in the electrolyte is 0.02% to 3.6%.

13. The lithium ion secondary battery according to claim 11, characterized in that: The mass percentage of the first additive in the electrolyte is 0.02% to 2%.

14. The lithium ion secondary battery according to claim 11, characterized in that: The mass percentage of the first additive in the electrolyte is 0.1% to 1.6%.

15. The lithium ion secondary battery according to any one of claims 1 to 7, characterized in that: The additive includes a negative electrode film-forming additive different from the first additive.

16. The lithium ion secondary battery according to any one of claims 1 to 7, characterized in that: The additive includes one or more of a second additive, a third additive, and a fourth additive; The second additive is one or more of a silane additive and a siloxane additive; The third additive is one or more of an isocyanate additive and an acid anhydride additive; The fourth additive is one or more of a lithium salt additive and a phosphate ester additive.

17. The lithium ion secondary battery according to claim 16, characterized in that: In the electrolyte, the mass ratio of the second additive to the first additive is 0.1-50.

18. The lithium ion secondary battery according to claim 16, characterized in that: In the electrolyte, the mass ratio of the third additive to the first additive is 0.01-50.

19. The lithium ion secondary battery according to claim 16, characterized in that: In the electrolyte, the mass ratio of the fourth additive to the first additive is 0.1-100.

20. The lithium ion secondary battery according to claim 16, characterized in that: In the electrolyte, the mass ratio of the second additive, the third additive, the fourth additive and the first additive is (0-0.5):(0-0.5):(0-1):

1.

21. The lithium ion secondary battery according to any one of claims 1 to 7, characterized in that: The electrolyte satisfies one or more of the following characteristics: (c1) the molecular weight of the first additive is less than or equal to 500 Da; (c2) the molecule of the first additive contains 1 to 4 carbon-carbon triple bonds; (c3) the carbon-carbon triple bond is CH≡C-; (c4) the first additive contains 1 to 4 Lewis base nitrogen heterocycles in its molecule; (c5) the Lewis base nitrogen heterocycle includes an imidazole ring; (c6) In the molecule of the first additive, the carbon-carbon triple bond and the Lewis base nitrogen heterocycle are connected via a linker L1, and the linker L1 contains a C 1-3 Alkylene or containing a fluorinated C covalently bonded to a carbon-carbon triple bond 1-3 Alkylene.

22. The lithium ion secondary battery according to claim 21, characterized in that: The first additive satisfies one or more of the following characteristics: (d1) the molecular weight of the first additive is less than or equal to 300 Da; (d2) the first additive contains 1 to 4 imidazole rings in its molecule; (d3) The linker L1 contains a C covalently bonded to a carbon-carbon triple bond. 1-3 Alkylene; (d4) The Lewis base nitrogen heterocycle includes an imidazole ring; the imidazole ring in the Lewis base nitrogen heterocycle is substituted by 0, 1 or more substituent groups Q2, and the substituent groups Q2 in the substituted imidazole group are each independently C 1-3 an alkyl group, a cyano group or a fluorine atom.

23. The lithium ion secondary battery according to claim 21, characterized in that: The first additive includes a compound II having a structure as shown in formula (II): Among them, L 11 C 1-3 Alkylene, Q2 is independently C 1-3 Alkyl, cyano or fluorine atom, p2 is 0, 1, 2 or 3; The mass proportion of the compound II in the first additive is 80% to 100%.

24. A method for preparing a lithium ion secondary battery, characterized in that: The steps include: An electrode assembly including a positive electrode sheet, a separator and a negative electrode sheet is placed in a battery housing; wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet; wherein the positive electrode sheet includes a positive electrode active layer, the positive electrode active layer includes a positive electrode active material, the positive electrode active material includes a lithium transition metal oxide positive electrode material, and the D v 3 greater than or equal to 1 μm; An electrolyte is injected into the battery housing, and the electrolyte is allowed to stand to allow the electrolyte to soak the positive electrode plate and the negative electrode plate to form an electrolyte; wherein the electrolyte includes an electrolyte salt, a non-aqueous solvent and an additive; the additive includes a first additive, and the first additive is an acetylene base additive containing a Lewis base nitrogen heterocycle.

25. The method for preparing a lithium ion secondary battery according to claim 24, characterized in that: A lithium ion secondary battery as claimed in any one of claims 2 to 23 is prepared.

26. An electrical device, characterized in that: A lithium ion secondary battery comprising any one of claims 1 to 23.

Citation Information

Patent Citations

  • Non-aqueous electrolyte for lithium secondary battery and lithium secondary battery comprising same

    CN113711415A

  • Lithium ion battery and electric device

    CN118693353A

  • Battery cell, battery device, and electric device

    CN119153758A

  • Positive electrode active material and preparation method thereof, sodium ion battery and electric equipment

    CN119361664A

  • Secondary battery and electrical device

    WO2024207433A1